Core-shell quantum dots, methods for making the same, quantum dot groups, quantum dot complexes, quantum dot compositions, and display devices

By adopting a core shell quantum dot structure of zinc, tellurium and selenium, and adding chloride during shell formation, the problem of insufficient optical properties of cadmium-free quantum dots in the prior art is solved, and the optical properties of high efficiency and narrow FWHM are achieved.

CN112680211BActive Publication Date: 2025-03-11SAMSUNG ELECTRONICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011109701.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-17
Filing Date
2020-10-16
Publication Date
2025-03-11
Estimated Expiration
2040-10-16

AI Technical Summary

Technical Problem

It is difficult to develop cadmium-free quantum dots, and quantum dots based on group III-V compounds are difficult to achieve narrow half-width and high quantum efficiency while emitting the desired wavelength.

Method used

A core shell quantum dot structure including zinc, tellurium and selenium is adopted to control the shape and optical properties of the particles by forming a semiconductor nanocrystal shell composed of zinc, selenium and sulfur on the core particles, and chloride is added during shell formation.

Benefits of technology

Improved optical properties of cadmium-free quantum dots, including improved luminescence efficiency and stability, and enable a narrow FWHM in the desired wavelength range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112680211B_ABST
    Figure CN112680211B_ABST
Patent Text Reader

Abstract

The present invention relates to core-shell quantum dots, methods for making the same, quantum dot groups, quantum dot composites, quantum dot compositions, and display devices. Disclosed are core-shell quantum dots and their manufacture, the core-shell quantum dots comprising: a core comprising a first semiconductor nanocrystal, the first semiconductor nanocrystal comprising zinc, tellurium, and selenium; and a semiconductor nanocrystal shell disposed on the core, the semiconductor nanocrystal shell comprising zinc, and selenium, sulfur, or a combination thereof, wherein the core-shell quantum dots do not include cadmium, lead, mercury, or a combination thereof, wherein the core-shell quantum dots comprise chlorine, wherein in the core-shell quantum dots, the molar ratio of chlorine to tellurium is greater than or equal to about 0.01:1, and wherein the quantum efficiency of the core-shell quantum dots is greater than or equal to about 10%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefits of Korean Patent Application No. 10-2019-0129447 filed in the Korean Intellectual Property Office on October 17, 2019, and all rights arising therefrom, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Disclosed are core-shell quantum dots, methods for making the same, and electronic devices comprising the same. Background Art

[0004] Different from bulk (body) materials, the physical properties (e.g., band gap and melting point) of nanoparticles can be controlled by changing the size of the nanoparticles. For example, semiconductor nanocrystal particles (also referred to as quantum dots) are crystalline materials with a size of several nanometers. Semiconductor nanocrystal particles have a relatively small size and a surface area per unit volume that is large, presenting a quantum confinement effect and having properties different from bulk materials with the same composition. Quantum dots can absorb light from an excitation source and become excited, emitting energy corresponding to the band gap energy of the quantum dots. Summary of the invention

[0005] Embodiments provide cadmium-free quantum dots that can achieve enhanced, eg, improved, optical properties such as luminous efficiency and stability (eg, oxidative stability).

[0006] Embodiments provide methods of making the aforementioned cadmium-free quantum dots.

[0007] Embodiments provide a quantum dot composite including the aforementioned cadmium-free quantum dots.

[0008] Embodiments provide electronic devices (eg, display devices) including the aforementioned cadmium-free quantum dots.

[0009] In an embodiment, a core-shell quantum dot (hereinafter, also referred to as a quantum dot) includes: a core including a first semiconductor nanocrystal, the first semiconductor nanocrystal including zinc, tellurium, and selenium; and a semiconductor nanocrystal shell disposed on the core, the semiconductor nanocrystal shell including zinc; and selenium, sulfur, or a combination thereof,

[0010] wherein the core-shell quantum dots do not include cadmium, lead, mercury, or a combination thereof,

[0011] wherein the core-shell quantum dots further comprise chlorine, and

[0012] The core-shell quantum dots have a quantum efficiency greater than or equal to about 10%.

[0013] In the core-shell quantum dots, a molar ratio of chlorine to tellurium (Cl:Te) is greater than or equal to about 0.01:1.

[0014] The core-shell quantum dots may have a quantum efficiency of greater than or equal to about 15%, greater than or equal to about 20%, greater than or equal to about 25%, greater than or equal to about 30%, greater than or equal to about 35%, greater than or equal to about 40%, greater than or equal to about 45%, or greater than or equal to about 50%.

[0015] In the core, a molar ratio of tellurium to selenium may be greater than or equal to about 0.2:1 and less than or equal to about 5:1.

[0016] The core-shell quantum dots may have a molar ratio of tellurium to selenium (Te:Se) of greater than or equal to about 0.05:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.1:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.15:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.4:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.5:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 1:1, greater than or equal to about 1.1:1, or greater than or equal to about 1.2:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 1.3:1, or greater than or equal to about 1.5:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 1.9:1. The molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 2:1.

[0017] The core-shell quantum dots may have a molar ratio of tellurium to selenium (Te:Se) of less than or equal to about 4:1. The molar ratio of tellurium to selenium (Te:Se) may be less than or equal to about 3:1. The molar ratio of tellurium to selenium (Te:Se) may be less than or equal to about 2.5:1, or less than or equal to about 2.2:1. The molar ratio of tellurium to selenium (Te:Se) may be less than or equal to about 2:1, less than or equal to about 1.8:1, less than or equal to about 1.7:1, less than or equal to about 1.6:1, less than or equal to about 1.5:1, or less than or equal to about 1.4:1.

[0018] In the core-shell quantum dots, the molar ratio of tellurium to zinc (Te:Zn) may be greater than or equal to about 0.05: 1. In the core-shell quantum dots, the molar ratio of tellurium to zinc (Te:Zn) may be greater than or equal to about 0.1: 1, or greater than or equal to about 0.2: 1. In the core-shell quantum dots, the molar ratio of tellurium to zinc (Te:Zn) may be greater than or equal to about 0.3: 1, greater than or equal to about 0.35: 1, or greater than or equal to about 0.4: 1.

[0019] The core-shell quantum dots may have a molar ratio of chlorine to tellurium (Cl:Te) of greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, or greater than or equal to about 0.35:1. In the core-shell quantum dots, the molar ratio of chlorine to tellurium may be greater than or equal to about 0.4:1.

[0020] The core-shell quantum dots may further include aluminum, lithium, or a combination thereof. In an embodiment, the core-shell quantum dots may not include manganese, copper, or a combination thereof.

[0021] In an embodiment, the core-shell quantum dots may not include a III-V compound. The III-V compound may include indium, gallium, or a combination thereof. In an embodiment, the core-shell quantum dots may not include indium phosphide or its alloy (eg, InZnP).

[0022] In an embodiment, the core-shell quantum dots may not include bromine, iodine, or a combination thereof. The core-shell quantum dots may further include fluorine.

[0023] In X-ray photoelectron spectroscopy (XPS) analysis, the core-shell quantum dots may not show a peak of tellurium oxide.

[0024] In XPS analysis or time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis, the core-shell quantum dots may or may not exhibit a peak of fluorine.

[0025] In XPS analysis or time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis, the core-shell quantum dots may exhibit a peak of chlorine (Cl2P).

[0026] The maximum photoluminescence peak of the core-shell quantum dots may be within a wavelength range of greater than or equal to about 470 nanometers (nm). The maximum photoluminescence peak of the core-shell quantum dots may be within a wavelength range of greater than or equal to about 480 nm. The maximum photoluminescence peak of the core-shell quantum dots may be within a wavelength range of greater than or equal to about 500 nm. The maximum photoluminescence peak of the core-shell quantum dots may be within a wavelength range of less than or equal to about 600 nm, for example, less than or equal to about 590 nm, less than or equal to about 580 nm, less than or equal to about 570 nm, or less than or equal to about 560 nm.

[0027] The ultraviolet-visible (UV-Vis) absorption spectrum of the core-shell quantum dots may include a first absorption peak and a valley adjacent thereto.

[0028] The maximum photoluminescence peak of the core-shell quantum dots may have a half width (FWHM) of less than about 50 nm, less than or equal to about 45 nm, less than or equal to about 40 nm, less than or equal to about 35 nm, less than or equal to about 34 nm, less than or equal to about 33 nm, less than or equal to about 32 nm, or less than or equal to about 31 nm.

[0029] The maximum photoluminescence peak of the core-shell quantum dots may be within a wavelength range of less than or equal to about 540 nm and greater than or equal to about 500 nm, and may have a FWHM of less than or equal to about 33 nm. The maximum photoluminescence peak of the core-shell quantum dots may be within a wavelength range of greater than or equal to about 540 nm and less than or equal to about 580 nm, and may have a FWHM of less than or equal to about 35 nm.

[0030] The core-shell quantum dots may have a quantum efficiency of greater than or equal to about 12%, greater than or equal to about 20%, greater than or equal to about 30%, or greater than or equal to about 35%.

[0031] The first semiconductor nanocrystal or the core-shell quantum dot may include ZnTe x Se 1-x , wherein x is greater than or equal to about 0.4, greater than or equal to about 0.45, greater than or equal to about 0.5 and less than or equal to about 0.9, less than or equal to about 0.8, less than or equal to about 0.7.

[0032] The semiconductor nanocrystalline shell may include selenium and sulfur. The semiconductor nanocrystalline shell may include ZnSe, ZnS, ZnSeS, or a combination thereof.

[0033] The core-shell quantum dots may have a ratio of greater than 0:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.8:1, greater than or equal to about 1:1, or greater than or equal to about 1.2:1 and less than or equal to about 8:1, less than or equal to about 7.5:1, less than or equal to about The molar ratio of sulfur to selenium (S / Se) may be in the range of 0.1:1-8:1, 0.2:1-7:1, 0.3:1-6:1, 0.4:1-5:1, 0.5:1-4:1, 0.6:1-3:1, 0.7:1-2:1, 0.8:1-1:1, or a combination thereof.

[0034] The core-shell quantum dots may have a sphalerite crystal structure in an X-ray diffraction analysis.

[0035] The core-shell quantum dots may include organic ligands, and the organic ligands may include RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, RH 2 PO, R 2 HPO, R 3 PO, RH 2 P.R 2 HP, R 3 P、ROH、RCOOR'、RHPO(OH)、RPO(OH) 2 , R 2 POOH, a polymeric organic ligand, or a combination thereof, wherein R and R' are the same or different and are each independently a substituted or unsubstituted C1-C40 aliphatic hydrocarbon group, a substituted or unsubstituted C6-C40 aromatic hydrocarbon group, or a combination thereof.

[0036] In an embodiment, the organic ligand may not include a multifunctional organic compound having a thiol moiety, and an amino group, a carboxylic acid group, or a combination thereof. In an embodiment, the organic ligand may not include a glutathione compound.

[0037] The core-shell quantum dots may be water-insoluble. When dispersed in water, the core-shell quantum dots may exhibit, for example, exhibit, an average particle size of greater than or equal to about 500 nm as determined by dynamic light scattering (DLS) analysis.

[0038] When dispersed in an organic solvent (eg, toluene, octane, etc.), the core-shell quantum dots can be configured to form an organic solution having an average particle size of less than or equal to about 200 nm as determined by DLS analysis.

[0039] In an embodiment, the quantum dot group includes a plurality of the aforementioned quantum dots, wherein an average circularity of the plurality of the aforementioned quantum dots may be greater than or equal to about 0.70.

[0040] The average circularity of the core-shell quantum dots may be greater than or equal to about 0.75. The average circularity of the core-shell quantum dots may be greater than or equal to about 0.80, or greater than or equal to about 0.82.

[0041] The average solidity may be greater than or equal to about 0.8, greater than or equal to about 0.85, or greater than or equal to about 0.9.

[0042] The average particle size of the core-shell quantum dots may be greater than or equal to about 3 nm, greater than or equal to about 3.5 nm, greater than or equal to about 4 nm, greater than or equal to about 4.5 nm, greater than or equal to about 5 nm, greater than or equal to about 5.5 nm, greater than or equal to about 6 nm, greater than or equal to about 6.5 nm, greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, or greater than or equal to about 10 nm. The average particle size of the core-shell quantum dots may be less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 35 nm, less than or equal to about 30 nm, less than or equal to about 25 nm, less than or equal to about 20 nm, less than or equal to about 15 nm, less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, less than or equal to about 7 nm, less than or equal to about 6 nm, less than or equal to about 5 nm, or less than or equal to about 4 nm.

[0043] In an embodiment, a method of making the core-shell quantum dots comprises:

[0044] preparing a zinc precursor organic solution comprising a zinc precursor and a first organic ligand in a first organic solvent; and

[0045] While the zinc precursor organic solution is heated, a first selenium precursor, a tellurium precursor, a metal hydride compound, and a second organic ligand are added to the zinc precursor organic solution to prepare core particles, and

[0046] reacting a zinc precursor with a second selenium precursor, a sulfur precursor, or a combination thereof in a third organic solvent in the presence of the core particle and a shell-forming organic ligand to form a semiconductor nanocrystal shell on the core particle, and

[0047] The chlorine precursor is added to the reaction system during preparation of the core particle, during formation of the semiconductor nanocrystal shell, or during preparation of the core particle and during formation of the semiconductor nanocrystal shell (eg, at a first reaction temperature or the shell formation temperature).

[0048] The method may further include adding a fluorine precursor to the reaction system during the preparation of the core particle, during the formation of the semiconductor nanocrystal shell, or during the preparation of the core particle and during the formation of the semiconductor nanocrystal shell.

[0049] The method may further include preparing a chlorine precursor by dissolving a chlorine compound in a fourth organic solvent.

[0050] In an embodiment, the tellurium precursor may include tellurium dispersed in a second organic solvent, and a concentration of tellurium in the tellurium precursor is greater than about 0.1 mol / liter (M) or greater than about 0.15M.

[0051] In the preparation of the core, the molar ratio of tellurium added to the reaction system relative to selenium added may be greater than about 0.25:1, for example, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, or greater than or equal to about 0.6:1.

[0052] The first reaction temperature may be greater than or equal to about 280° C. The shell formation temperature may be greater than or equal to about 250° C. The method may further include mixing the tellurium precursor, the metal hydride compound, and the second organic ligand at a temperature less than about 80° C. to form a single mixed solution before adding to the zinc precursor organic solution.

[0053] The second organic ligand may include an aliphatic organic amine compound or a combination thereof.

[0054] The metal hydride compound may include lithium, aluminum, or a combination thereof. The metal hydride compound may include lithium aluminum hydride.

[0055] The chlorine compound may include a chloride of a multivalent metal (eg, zinc, gallium, aluminum, or a combination thereof).

[0056] The method may further include adding a fluorine compound to the reaction system. The amount of the chlorine precursor added, the amount of the fluorine compound added (if used), or the amount of the chlorine precursor added and the amount of the fluorine compound added may be greater than or equal to about 0.01 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.2 mole, or greater than or equal to about 0.3 mole per mole of sulfur (or one mole of selenium), and less than or equal to about 10 moles, less than or equal to about 5 moles, less than or equal to about 2 moles, or less than or equal to about 1 mole per mole of sulfur (or one mole of selenium).

[0057] The fourth organic solvent may include a C1-C30 alcohol solvent such as ethanol, methanol, etc., a C2-C30 ketone solvent, an organic phosphine solvent such as trioctylphosphine, or a combination thereof.

[0058] In an embodiment, a quantum dot (eg, polymer) composite comprises: a (eg, polymer) matrix; and a plurality of quantum dots dispersed in the (polymer) matrix,

[0059] The plurality of quantum dots include the aforementioned (core-shell) quantum dots.

[0060] The polymer matrix may include a cross-linked polymer, a binder polymer including carboxylic acid groups, or a combination thereof.

[0061] The cross-linked polymer may include a polymerization product of a photopolymerizable monomer including a carbon-carbon double bond, a polymerization product of the photopolymerizable monomer and a polythiol compound having at least two thiol groups (eg, at a terminal of the polythiol compound), or a combination thereof.

[0062] The core-shell quantum dot (eg, polymer) composite may further include metal oxide fine particles (eg, dispersed in the polymer matrix).

[0063] In an embodiment, a display device includes a light emitting element, and the light emitting element includes a plurality of the core-shell quantum dots.

[0064] In an embodiment, a display device includes a light emitting element (eg, a photoluminescent element) and optionally a light source, wherein the light emitting element includes the core-shell quantum dots or core-shell quantum dot polymer composite. If present, the light source may be configured to provide incident light to the light emitting element.

[0065] The incident light may have a photoluminescence peak wavelength of about 440 nm to about 560 nm (eg, about 440 nm to about 460 nm).

[0066] The light emitting element may include a sheet of the core-shell quantum dot polymer composite.

[0067] The light emitting element may include a stacked structure including a substrate and a light emitting layer (eg, a photoluminescent layer) disposed on the substrate.

[0068] The light emitting layer may include a pattern of the core-shell quantum dot polymer composite.

[0069] The pattern may include a repeating segment (portion) configured to emit light of a predetermined wavelength, for example, at least one (kind of) or two (kinds of) repeating segments.

[0070] The display device may be configured to have a color reproducibility of greater than or equal to about 80% according to the BT2020 standard.

[0071] In an embodiment, a quantum dot comprises: a core comprising a first semiconductor nanocrystal, the first semiconductor nanocrystal comprising zinc, tellurium, and selenium; and a semiconductor nanocrystal shell disposed on the core, the semiconductor nanocrystal shell comprising zinc, chlorine, and selenium, sulfur, or a combination thereof, wherein the average circularity of a plurality of core-shell quantum dots is greater than or equal to about 0.70.

[0072] In embodiments, cadmium-free quantum dots can be provided that are capable of emitting light at a desired wavelength (e.g., greater than about 470 nm) with improved, e.g., improved efficiency and reduced FWHM. The quantum dots of embodiments can be applied to, for example, a variety of display devices, biomarkers (biosensors, bioimaging), photodetectors, solar cells, hybrid composites, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] The above and other advantages and features of the present disclosure will become more apparent by further describing exemplary embodiments thereof in detail with reference to the accompanying drawings, in which:

[0074] Figure 1 A diagram illustrating the concept of particle solidity.

[0075] Figure 2 is a graph of absorption (arbitrary units (au)) versus wavelength (nm) illustrating the definition of valley depth for the UV-visible absorption spectrum of quantum dots according to embodiments.

[0076] Figure 3 is an exploded view of a display device according to an embodiment.

[0077] Figure 4A is a schematic cross-sectional view of a display device according to an embodiment.

[0078] Figure 4B is a schematic cross-sectional view of a display device according to an embodiment.

[0079] Figure 5is a schematic cross-sectional view of a display device according to an embodiment.

[0080] Figure 6 is a schematic cross-sectional view of a light emitting device according to an embodiment.

[0081] Fig. 7A : is a transmission electron microscopy (TEM) image of the quantum dots synthesized in Example 2.

[0082] Figure 7B is a transmission electron microscopy (TEM) image of the quantum dots synthesized in Comparative Example 2-1.

[0083] Figure 8 is a transmission electron microscopy (TEM) image of the quantum dots synthesized in Comparative Example 2-2. DETAILED DESCRIPTION

[0084] With reference to the following example embodiments together with the accompanying drawings attached hereto, the advantages and characteristics of the present disclosure, and the methods for realizing it will become clear. However, the embodiments should not be interpreted as being limited to the embodiments set forth herein. Unless otherwise defined, all terms (including technical and scientific terms) used in this specification can be used by the meanings commonly understood by personnel with common knowledge in the art. The terms defined in the common dictionary cannot be interpreted ideally or exaggeratedly, unless clearly defined. In addition, unless explicitly described to the contrary, the word "including (comprising)" will be understood to mean including the stated elements, but does not exclude any other elements.

[0085] In addition, the singular includes the plural, unless otherwise mentioned. As used herein, "a (a), "an", "said", and "at least one" do not represent a limit to quantity, and are intended to include both the singular and the plural, unless the context clearly states otherwise. For example, "(a) element" has the same meaning as "at least one element", unless the context clearly states otherwise. "At least one" should not be interpreted as limiting "a (a), "an". "Or" means "and / or".

[0086] In the drawings, the thickness of layers, films, panels, regions, etc., are exaggerated for clarity. The same reference numerals refer to the same elements throughout the specification.

[0087] It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. Conversely, when an element is referred to as being "directly on" another element, there are no intervening elements.

[0088] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or segments (parts), these elements, components, regions, layers and / or segments (parts) should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or segment (part) from another element, component, region, layer or segment (part). Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "segment (part)" discussed below may be referred to as a second element, component, region, layer or segment (part).

[0089] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as shown in the figure. It will be understood that, in addition to the orientation shown in the figure, relative terms are also intended to cover different orientations of the device. For example, if the device in one of the figures is turned over, the element described as being on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, depending on the specific orientation of the figure, the term "lower" may cover both "lower" and "upper" orientations. Similarly, if the device in one of the figures is turned over, the element described as "below" or "below" the other element will be oriented "above" the other element. Therefore, the term "below..." or "below..." may cover both "above..." and "below..." orientations.

[0090] As used herein, "about" includes the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±10% or 5% relative to the stated value.

[0091] Exemplary embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, deviations from the shapes of the figures as a result of, for example, manufacturing techniques and / or tolerances are expected. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as shown herein, but rather include deviations in shape caused by, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated sharp corners may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions, and are not intended to limit the scope of the claims.

[0092] As used herein, when no definition is otherwise provided, "substituted" may refer to a compound or group in which a hydrogen atom is replaced by a substituent such as a C1-C30 alkyl, a C2-C30 alkenyl, a C2-C30 alkynyl, a C6-C30 aryl, a C7-C30 alkaryl, a C1-C30 alkoxyl, a C1-C30 heteroalkyl, a C3-C30 heteroalkaryl, a C3-C30 cycloalkyl, a C3-C15 cycloalkenyl, a C6-C30 cycloalkynyl, a C2-C30 heterocycloalkyl, a halogen (-F, -Cl, -Br, or -I), a hydroxyl (-OH), a nitro (-NO), or a cycloalkyl. 2 ), cyano (-CN), amino (-NRR', wherein R and R' are independently hydrogen or C1-C6 alkyl), azido (-N 3 ), amidino (-C(=NH)NH 2 ), hydrazino (-NHNH 2 ), hydrazone (=N(NH 2 )), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2 ), thiol group (-SH), ester group (-C(=O)OR, wherein R is C1-C6 alkyl or C6-C12 aryl), carboxyl group (-COOH) or its salt (-C(=O)OM, wherein M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 , wherein M is an organic or inorganic cation), or a combination thereof.

[0093] As used herein, when no definition is provided otherwise, a hydrocarbon group refers to a group (e.g., an alkyl, alkenyl, alkynyl, or aryl) comprising carbon and hydrogen (or consisting of carbon and hydrogen). A hydrocarbon group may be a group having a valence of 1 or greater formed by removing a hydrogen atom, e.g., at least one hydrogen atom, from an alkane, an alkene, an alkyne, or an aromatic hydrocarbon. In a hydrocarbon group, a methylene group, e.g., at least one methylene group, may be replaced by an oxygen moiety, a carbonyl moiety, an ester moiety, -NH-, or a combination thereof.

[0094] As used herein, when no definition is otherwise provided, "aliphatic" refers to a saturated or unsaturated straight chain or branched hydrocarbon group. The aliphatic group may be, for example, an alkyl, alkenyl, or alkynyl group.

[0095] As used herein, when no definition is otherwise provided, "alkyl" refers to a linear or branched, saturated, monovalent hydrocarbon group (methyl, ethyl, hexyl, etc.).

[0096] As used herein, when a definition is not otherwise provided, "alkenyl" refers to a straight-chain or branched monovalent hydrocarbon group having one or more carbon-carbon double bonds.

[0097] As used herein, when a definition is not otherwise provided, "alkynyl" refers to a straight-chain or branched monovalent hydrocarbon group having one or more carbon-carbon triple bonds.

[0098] As used herein, when no definition is otherwise provided, "aromatic" refers to an organic compound or group that includes an unsaturated cyclic group having delocalized π electrons, such as at least one unsaturated cyclic group having delocalized π electrons. The term encompasses both hydrocarbon aromatic compounds and heteroaromatic compounds.

[0099] As used herein, when a definition is not otherwise provided, "aryl" refers to a group formed by removing hydrogen, for example, at least one hydrogen, from an aromatic hydrocarbon (eg, phenyl or naphthyl).

[0100] As used herein, when no definition is otherwise provided, "hetero" refers to one or more (eg, 1-3) heteroatoms including N, O, S, Si, P, or a combination thereof.

[0101] As used herein, "Group" refers to a Group of the Periodic Table.

[0102] As used herein, “Group III” may refer to Group IIIA and Group IIIB, and examples of Group III metals may be In, Ga, and Tl, but are not limited thereto.

[0103] As used herein, “Group V” may refer to Group VA, and examples may include nitrogen, phosphorus, arsenic, antimony, and bismuth, but are not limited thereto.

[0104] In embodiments, "circularity" may refer to the definition as provided in the ImageJ User Guide (v 1.46r) and may be defined as follows:

[0105] 4x((area) / (πx(major axis) 2 )).

[0106] Roundness may correspond to the inverse of the aspect ratio (length to diameter ratio). The aspect ratio may be the ratio of the major axis to the minor axis. "Area" may be the area of ​​a two-dimensional image of a given particle, and the major axis may refer to the major axis of the best-fit elliptical shape of a given image. Roundness may be as follows: It may reflect the ratio between the inscribed circle and the circumscribed circle for a given object.

[0107] As used herein, the term "solidity" refers to the ratio of the area (B) of the two-dimensional region of a quantum dot relative to the area (A) of the convex hull. The convex hull may be defined as the smallest convex set of points in which the set of all points constituting the two-dimensional image of a given quantum dot obtained by electron microscopy analysis is contained. In other words, the convex hull may be defined as the smallest convex polygon in which the set of all points constituting the two-dimensional image of a given quantum dot obtained by electron microscopy analysis is contained (see Figure 1 ). Solidity can be measured by transmission electron microscopy analysis. For example, commercially available computer programs (e.g., image processing programs such as "image J") can be used to calculate (the average value of) solidity from transmission electron microscopy (TEM) images of quantum dots.

[0108] As used herein, the term "valley" of the UV-visible absorption spectrum refers to the portion where the slope of the tangent line of the UV-visible absorption spectrum curve changes from a negative value to a positive value as the wavelength increases (see Figure 2 The valley may exist near the first absorption peak 1 (see Figure 2 ).

[0109] In the UV-visible absorption spectrum of the (core or core-shell) quantum dot, the depth of the valley adjacent to the first absorption peak (ie, valley depth (VD)) can be defined by the following equation:

[0110] (Abs 第一 -Abs 谷 ) / Abs 第一 =VD

[0111] Among them Abs 第一 is the absorption intensity at the wavelength of the first absorption peak, and Abs 谷 is the absorption intensity at the lowest point of the valley.

[0112] As used herein, the term "first absorption peak wavelength" refers to the wavelength of the main exciton peak that appears first from the longest wavelength region of the ultraviolet-visible absorption spectrum of the quantum dot (i.e., appears in the lowest energy region of the ultraviolet-visible absorption spectrum).

[0113] As used herein, an "average" (eg, an average size of quantum dots) may be a mean or a median. In embodiments, the average may be a "mean" average.

[0114] As used herein, quantum efficiency may be a relative quantum yield or an absolute quantum yield that can be easily measured by any commercially available equipment. Quantum efficiency (or quantum yield) can be measured in a solution state or a solid state (with a complex). In an embodiment, "quantum yield (or quantum efficiency)" may be the ratio of photons emitted (for example, by a group of nanostructures or nanostructures) to photons absorbed. In an embodiment, quantum efficiency may be measured by any method. For example, there may be two methods for measuring fluorescence quantum yield or efficiency: an absolute method and a relative method. The absolute method directly obtains quantum yield by: detecting all sample fluorescence using an integrating sphere. In a relative method, the fluorescence intensity of a standard sample (for example, a standard dye) can be compared with the fluorescence intensity of an unknown sample to calculate the quantum yield of the unknown sample. Depending on its photoluminescence (PL) wavelength, coumarin 153, coumarin 545, rhodamine 101 inner salt, anthracene, and rhodamine 6G can be used as standard dyes, but are not limited thereto.

[0115] The quantum yield (QY) can be easily and reproducibly determined by using a commercially available apparatus (eg, from Hitachi Co. Ltd or Hamamatsu Co. Ltd) and referring to the manual provided by the manufacturer.

[0116] The FWHM and the maximum PL peak wavelength can be determined by a photoluminescence spectrum obtained by a spectrophotometer (or fluorescence spectrophotometer).

[0117] As used herein, the expression "does not include cadmium (or other harmful heavy metals)" may refer to the following: wherein the concentration of cadmium (or harmful heavy metals) may be less than or equal to about 100 parts per million by weight (ppmw), less than or equal to about 50 ppmw, less than or equal to about 10 ppmw, less than or equal to about 1 ppmw, less than or equal to about 0.1 ppmw, less than or equal to about 0.01 ppmw, or about zero. In an embodiment, substantially no cadmium (or other heavy metal) may be present, or if present, the amount of cadmium (or other heavy metal) may be less than or equal to the detection limit of a given analytical tool (e.g., inductively coupled plasma atomic emission spectrometry) or as its impurity level.

[0118] Semiconductor nanocrystal particles (e.g., quantum dots) can absorb light from an excitation source and can emit light corresponding to the energy band gap of the quantum dots. The energy band gap of the quantum dots can change with their size and composition. For example, when the size of the quantum dots increases, the quantum dots can have a narrower energy band gap and can exhibit an increased luminescent wavelength. Semiconductor nanocrystals can be used as luminescent materials in a variety of fields such as display devices, energy devices, or bioluminescent devices.

[0119] Quantum dots with relatively improved photoluminescent properties may include toxic heavy metals such as cadmium (Cd), lead (Pb), mercury (Hg), or a combination thereof. Toxic heavy metals such as cadmium may cause environmental problems, health problems, or a combination thereof, and are one of the restricted elements in accordance with the Restriction of Hazardous Substances Directive (RoHS) in many countries. Therefore, it is desirable to develop cadmium-free quantum dots with improved photoluminescent properties. Cadmium-free indium phosphide quantum dots (QDs) may be applied, for example, for use in practical devices.

[0120] In order to be applied to quantum dot display devices (e.g., including a color conversion layer containing quantum dots), for example, for use therein, and to achieve a display device with relatively high color reproducibility according to the next generation color standard such as BT2020, it is desirable to have a relatively narrow half width (FWHM) of quantum dots. For example, in order for the device to achieve an improvement in color reproducibility according to the BT2020 standard, for example, it is desirable that the luminescent material used herein has a reduced level of FWHM, such as a narrower FWHM. However, compared with a Cd-based core (e.g., a CdSe core), a III-V compound-based quantum dot including indium and phosphorus has a smaller band gap and a larger Bohr radius, and the change in FWHM depending on the size of the quantum dot may be significant. Therefore, InP-based quantum dots may not be able to have a reduced level of FWHM, such as a narrower FWHM, while emitting light of a desired wavelength (e.g., greater than about 470nm, greater than or equal to about 475nm, greater than or equal to about 480nm and less than or equal to about 580nm). In addition, a core including indium and phosphorus may be sensitive to surface oxidation, and a quantum dot including the same may have an increased FWHM when including a shell, e.g., a shell coated on the core of the quantum dot, and achieving a desired level of quantum efficiency together with a desired FWHM may be difficult. Therefore, a quantum dot including a III-V compound (e.g., an InP-based core) may not show, e.g., exhibit a desirable FWHM, even if the quantum dot including the III-V compound has a desirable particle distribution within one monolayer thereof.

[0121] The present inventors have found that in the case of ZnTeSe based nanocrystalline particles as cadmium-free quantum dots, the wavelength differences caused by the particle distribution can be kept at a desirably low level and thus the resulting quantum dots can show, e.g., exhibit, a reduced level of FWHM, e.g., a narrower FWHM.

[0122] However, a quantum dot structure including a ZnTeSe-based core and an inorganic shell coated thereon may be difficult to exhibit desired dispersion properties (e.g., organic solvent dispersibility) and to show, for example, desired luminescence properties. Without wishing to be bound by any theory, according to the inventors' research, it is believed that the zinc telluride-based core is sensitive to tellurium oxidation (particularly during shell formation), and increasing the reaction temperature may be very difficult. Therefore, during shell growth, it may become difficult to control the shape of the particles, and the obtained particles may have an arbitrary shape such as a pod shape.

[0123] In an embodiment, a core-shell quantum dot (or hereinafter, quantum dot) includes: a core including a first semiconductor nanocrystalline material; and a semiconductor nanocrystalline shell disposed on (or on the surface of) the core and including zinc, and selenium, sulfur, or a combination thereof.

[0124] The core-shell quantum dots do not include cadmium, lead, mercury, or a combination thereof. The core-shell quantum dots of an embodiment further include chlorine. In the quantum dots, the molar ratio of chlorine to tellurium is greater than or equal to about 0.01:1. The quantum efficiency of the core-shell quantum dots is greater than about 10%. In an embodiment, "does not include cadmium (or an element)" may refer to the following: wherein the concentration of cadmium (or an element) may be less than or equal to about 50 parts per million (ppm) (e.g., ppmw), less than or equal to about 10 ppm (e.g., ppmw), or almost zero.

[0125] The core-shell quantum dot (or the core) may include a predetermined amount of tellurium. The amount of the components included in the quantum dots as described herein may be determined by appropriate analytical tools (e.g., inductively coupled plasma atomic emission spectroscopy (ICP-AES), X-ray photoelectron spectroscopy (XPS), ion chromatography, transmission electron microscopy energy dispersive X-ray spectroscopy (TEM-EDS), etc.).

[0126] The core may have a structure in which selenium is alloyed (doped) in zinc telluride crystals. In the core or in the quantum dot, the amount of tellurium may be greater than the amount of selenium.

[0127] In the quantum dot of the embodiment, the core may include a first semiconductor nanocrystal including zinc, tellurium, and selenium. The first semiconductor nanocrystal may include ZnTe x Se 1-x(where x is greater than or equal to about 0.2, greater than or equal to about 0.3, greater than or equal to about 0.4, greater than or equal to about 0.5, greater than or equal to about 0.51, greater than or equal to about 0.52, greater than or equal to about 0.53, greater than or equal to about 0.54, greater than or equal to about 0.55, greater than or equal to about 0.56, greater than or equal to about 0.57, greater than or equal to about 0.58, greater than or equal to about 0.59, greater than or equal to about 0.6, greater than or equal to about 0.61, greater than or equal to about 0.62, greater than or equal to about 0.63, greater than or equal to about 0.64, greater than or equal to about 0.65, greater than or equal to about 0.66, greater than or equal to about 0.67, greater than or equal to about 0.68, greater than or equal to about 0.69, greater than or equal to about 0.70, greater than or equal to about 0.71, greater than or equal to about 0.72, greater than or equal to about 0.73, greater than or equal to about 0.74, greater than or equal to about 0.75, or greater than or equal to about 0.8 and less than or equal to about 0.9, less than or equal to about 0.89, less than or equal to about 0.88, less than or equal to about 0.87, less than or equal to about 0.86, less than or equal to about 0.85, less than or equal to about 0.84, less than or equal to about 0.83, less than or equal to about 0.82, less than or equal to about 0.8, less than or equal to about 0.75, less than or equal to about 0.7, less than or equal to about 0.65, or less than or equal to about 0.6).

[0128] In the core, the molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, greater than or equal to about 0.3:1, greater than or equal to about 0.35:1, greater than or equal to about 0.4:1, greater than or equal to about 0.45:1, greater than or equal to about 0.5:1, greater than or equal to about 0.55:1, greater than or equal to about 0.6:1, greater than or equal to about 0.65:1, greater than or equal to about 0.7:1, greater than or equal to about 0.75:1, greater than or equal to about 0.8:1, greater than or equal to about 0.85:1, greater than or equal to about 0.9:1, greater than or equal to about 0.93:1, greater than or equal to about 0.95:1, greater than or equal to about The invention relates to a method of manufacturing a polyester film having a molecular weight of at least about 1:1, greater than or equal to about 1.1:1, greater than or equal to about 1.2:1, greater than or equal to about 1.3:1, greater than or equal to about 1.4:1, greater than or equal to about 1.5:1, greater than or equal to about 1.6:1, greater than or equal to about 1.7:1, greater than or equal to about 1.8:1, greater than or equal to about 1.9:1, greater than or equal to about 2:1, greater than or equal to about 2.1:1, greater than or equal to about 2.2:1, greater than or equal to about 2.3:1, greater than or equal to about 2.4:1, greater than or equal to about 2.5:1, greater than or equal to about 2.6:1, greater than or equal to about 2.7:1, greater than or equal to about 2.8:1, greater than or equal to about 2.9:1, or greater than or equal to about 3:1.

[0129] In the core, the molar ratio of tellurium to selenium (Te:Se) may be less than or equal to about 5:1, less than or equal to about 4.5:1, less than or equal to about 4:1, less than or equal to about 3.9:1, less than or equal to about 3.8:1, less than or equal to about 3.7:1, less than or equal to about 3.6:1, less than or equal to about 3.5:1, less than or equal to about 3.4:1, less than or equal to about 3.3:1, less than or equal to about 3.2:1, less than or equal to about 3.1:1, less than or equal to about 3:1, less than or equal to about 2.9:1, less than or equal to about 2.8:1, less than or equal to about 2.7:1, less than or equal to about 2.6:1, less than or equal to about 2.5:1, less than or equal to about 2.4 :1, less than or equal to about 2.3:1, less than or equal to about 2.2:1, less than or equal to about 2.1:1, less than or equal to about 2.0:1, less than or equal to about 1.9:1, less than or equal to about 1.8:1, less than or equal to about 1.7:1, less than or equal to about 1.6:1, less than or equal to about 1.5:1, less than or equal to about 1.4:1, less than or equal to about 1.3:1, less than or equal to about 1.2:1, less than or equal to about 1.1:1, less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.8:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.5:1, or less than or equal to about 0.4:1.

[0130] In the core-shell quantum dots of embodiments, the molar ratio of tellurium to selenium (Te:Se) may be greater than about 0.05:1, e.g., greater than or equal to about 0.055:1, greater than or equal to about 0.06:1, greater than or equal to about 0.065:1, or greater than or equal to about 0.07:1. In the quantum dots of the embodiments, the molar ratio of tellurium to selenium (Te:Se) may be greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, greater than or equal to about 0.3:1, greater than or equal to about 0.35:1, greater than or equal to about 0.4:1, greater than or equal to about 0.45:1, greater than or equal to about 0.5:1, greater than or equal to about 0.55:1, greater than or equal to about 0.6:1, greater than or equal to about 0.65:1, greater than or equal to about 0.7:1, greater than or equal to about 0.75:1, greater than or equal to about 0.8:1, greater than or equal to about 0.85:1, greater than or equal to about 0.9:1, or greater than or equal to about 0.9:1. greater than or equal to about 1:1, greater than or equal to about 1.1:1, greater than or equal to about 1.2:1, greater than or equal to about 1.3:1, greater than or equal to about 1.4:1, greater than or equal to about 1.5:1, greater than or equal to about 1.6:1, greater than or equal to about 1.7:1, greater than or equal to about 1.8:1, greater than or equal to about 1.9:1, greater than or equal to about 2:1, greater than or equal to about 2.1:1, greater than or equal to about 2.2:1, greater than or equal to about 2.3:1, greater than or equal to about 2.4:1, greater than or equal to about 2.5:1, greater than or equal to about 2.6:1, greater than or equal to about 2.7:1, greater than or equal to about 2.8:1, greater than or equal to about 2.9:1, or greater than or equal to about 3:1.

[0131] In the quantum dots of the embodiments, the molar ratio of tellurium to selenium may be less than or equal to about 4:1, less than or equal to about 3.9:1, less than or equal to about 3.8:1, less than or equal to about 3.7:1, less than or equal to about 3.6:1, less than or equal to about 3.5:1, less than or equal to about 3.4:1, less than or equal to about 3.3:1, less than or equal to about 3.2:1, less than or equal to about 3.1:1, less than or equal to about 3:1, less than or equal to about 2.9:1, less than or equal to about 2.8:1, less than or equal to about 2.7:1, less than or equal to about 2.6:1, less than or equal to about 3.8 ...9:1, less than or equal to about 3.8:1, less than or equal to about 3.9:1, less than or equal to about 3.8:1, less than or equal to about 3.9:1, less less than or equal to about 2.5:1, or less than or equal to about 2.4:1, less than or equal to about 2.3:1, less than or equal to about 2.2:1, less than or equal to about 2.1:1, less than or equal to about 2.0:1, less than or equal to about 1.9:1, less than or equal to about 1.8:1, less than or equal to about 1.7:1, less than or equal to about 1.6:1, less than or equal to about 1.5:1, less than or equal to about 1.4:1, less than or equal to about 1.3:1, less than or equal to about 1.2:1, less than or equal to about 1.1:1, less than or equal to about 1:1, or less than or equal to about 0.9:1.

[0132] In the quantum dots of the embodiment, the molar ratio of tellurium to zinc (Te:Zn) may be greater than about 0.03: 1. In the quantum dots of the embodiment, the molar ratio of tellurium to zinc (Te:Zn) may be greater than or equal to about 0.05: 1, greater than or equal to about 0.07: 1, greater than or equal to about 0.09: 1, greater than or equal to about 0.1: 1, greater than or equal to about 0.13: 1, greater than or equal to about 0.15: 1, greater than or equal to about 0.17: 1, greater than or equal to about 0.19: 1, greater than or equal to about 0.2: 1, greater than or equal to about 0.21: 1, greater than or equal to about 0.23: 1, greater than or equal to about 0.25: 1, greater than or equal to about 0.3: 1, greater than or equal to about 0.35: 1, or greater than or equal to about 0.4: 1. In the quantum dots of the embodiments, the molar ratio of tellurium to zinc (Te:Zn) may be less than about 1:1, e.g., less than or equal to about 0.9:1, less than or equal to about 0.8:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.5:1, less than or equal to about 0.4:1, less than or equal to about 0.3:1, less than or equal to about 0.2:1, or less than or equal to about 0.1:1 (e.g., when determined by inductively coupled plasma atomic emission spectrometry analysis).

[0133] In the quantum dots of the embodiments, the molar ratio of zinc to tellurium (Zn:Te) may be greater than about 0.5:1, greater than or equal to about 1:1, greater than or equal to about 1.1:1, greater than or equal to about 1.5:1, greater than or equal to about 2:1, greater than or equal to about 3:1, greater than or equal to about 4:1, greater than or equal to about 5:1, greater than or equal to about 6:1, greater than or equal to about 7:1, greater than or equal to about 8:1, greater than or equal to about 9:1, greater than or equal to about 10:1, or greater than or equal to about 15:1 and less than or equal to about 40:1, less than or equal to about 35:1, less than or equal to about 30:1, less than or equal to about 25:1, less than or equal to about 20:1, less than or equal to about 15:1, less than or equal to about 10:1, less than or equal to about 6:1, less than or equal to about 4:1, less than or equal to about 3:1, or less than or equal to about 2.5:1.

[0134] The quantum dots of the embodiment may further include sulfur. In the embodiment, the molar ratio of sulfur to zinc may be greater than or equal to about 0.05:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, greater than or equal to about 0.3:1, or greater than or equal to about 0.35:1 and less than or equal to about 0.95:1, less than or equal to about 0.9:1, less than or equal to about 0.85:1, less than or equal to about 0.8:1, less than or equal to about 0.75:1, less than or equal to about 0.7:1, less than or equal to about 0.65:1, less than or equal to about 0.6:1, less than or equal to about 0.5:1, less than or equal to about 0.4:1, or less than or equal to about 0.3:1.

[0135] In the core-shell quantum dots of the embodiment, the molar ratio of sulfur to tellurium (S / Te) may be greater than 0, greater than or equal to about 0.1:1, greater than or equal to about 0.2:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, or greater than or equal to about 0.5:1 and less than or equal to about 8:1, less than or equal to about 7:1, less than or equal to about 6:1, less than or equal to about 5:1, less than or equal to about 4.5:1, less than or equal to about 4:1, less than or equal to about 3.5:1, less than or equal to about 3:1, less than or equal to about 2.5:1, less than or equal to about 2:1, less than or equal to about 1.5:1, less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.8:1, or less than or equal to about 0.7:1.

[0136] In the quantum dot, or the core (or the first semiconductor nanocrystal), the amount of tellurium may be greater than the amount of selenium.

[0137] In a quantum dot of an embodiment or in its core (or first semiconductor nanocrystal), the molar ratio of selenium to tellurium (Se:Te) may be greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, greater than or equal to about 0.3:1, greater than or equal to about 0.35:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.55:1, greater than or equal to about 0.6:1, greater than or equal to about 0.65:1, greater than or equal to about 0.7:1, greater than or equal to about 0.75:1, greater than or equal to about 0.8:1, greater than or equal to about 0.85:1, greater than or equal to about 0.9:1, or greater than or equal to about 0.95:1.

[0138] In a quantum dot of an embodiment or in its core (or first semiconductor nanocrystal), the molar ratio of selenium to tellurium (Se:Te) may be greater than or equal to about 1:1, greater than or equal to about 1.5:1, greater than or equal to about 2:1, greater than or equal to about 2.5:1, greater than or equal to about 3:1, greater than or equal to about 3.5:1, greater than or equal to about 4:1, greater than or equal to about 4.5:1, greater than or equal to about 5:1, or greater than or equal to about 5.5:1.

[0139] In an embodiment of the quantum dot or in its core (or first semiconductor nanocrystal), the molar ratio of selenium to tellurium (Se:Te) may be less than or equal to about 7:1, less than or equal to about 6.5:1, less than or equal to about 6:1, less than or equal to about 5.5:1, less than or equal to about 5:1, less than or equal to about 4.5:1, less than or equal to about 4:1, less than or equal to about 3.5:1, less than or equal to about 3:1, less than or equal to about 2.5:1, less than or equal to about 2:1, less than or equal to about 1.5:1, less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.85:1, less than or equal to about 0.8:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.5:1, or less than or equal to about 0.45:1.

[0140] In the quantum dots of the embodiment, the molar ratio of the sum of sulfur and selenium to tellurium ((Se+S) / Te) may be less than or equal to about 15:1, less than or equal to about 14:1, less than or equal to about 13:1, less than or equal to about 12:1, less than or equal to about 11:1, less than or equal to about 10:1, less than or equal to about 9:1, less than or equal to about 8:1, less than or equal to about 7:1, less than or equal to about 6:1, less than or equal to about 5:1, less than or equal to about 4:1, less than or equal to about 3:1, or less than or equal to about 2:1. In the core-shell quantum dots of the embodiment, the molar ratio of the sum of sulfur and selenium to tellurium may be greater than or equal to about 0.1:1, greater than or equal to about 0.5:1, greater than or equal to about 1:1, greater than or equal to about 1.5:1, or greater than or equal to about 2:1.

[0141] In an embodiment, the quantum dots may not include manganese, copper, or a combination thereof. The quantum dots may not include a III-V compound. In an embodiment, the III-V compound may include indium phosphide, indium zinc phosphide, gallium phosphide, or a combination thereof. The core-shell quantum dots may not exhibit a peak attributable to a III-V compound (e.g., indium phosphide or gallium phosphide) in an X-ray diffraction analysis.

[0142] The core-shell quantum dots of the embodiments may further include gallium, aluminum, lithium, or a combination thereof, for example, in the core, the semiconductor nanocrystal shell, or a combination thereof. In the quantum dots of the embodiments, the semiconductor nanocrystal shell may not include gallium, aluminum, lithium, or a combination thereof. In the quantum dots of the embodiments, the semiconductor nanocrystal shell may include gallium, aluminum, lithium, or a combination thereof.

[0143] In the quantum dots of the embodiments, if present, the molar ratio of gallium, aluminum, lithium, or a combination thereof to tellurium may be greater than or equal to about 0.005:1, greater than or equal to about 0.009:1, greater than or equal to about 0.01:1, greater than or equal to about 0.02:1, greater than or equal to about 0.03:1, greater than or equal to about 0.04:1, greater than or equal to about 0.05:1, greater than or equal to about 0.06:1, greater than or equal to about 0.07:1, greater than or equal to about 0.08:1, greater than or equal to about 0.09:1, or greater than or equal to about 0.10:1. :1, greater than or equal to about 0.1:1, greater than or equal to about 0.11:1, greater than or equal to about 0.12:1, greater than or equal to about 0.13:1, greater than or equal to about 0.14:1, greater than or equal to about 0.15:1, greater than or equal to about 0.16:1, greater than or equal to about 0.17:1, greater than or equal to about 0.18:1, greater than or equal to about 0.19:1, greater than or equal to about 0.2:1, greater than or equal to about 0.21:1, greater than or equal to about 0.22:1, greater than or equal to about 0. 23:1, greater than or equal to about 0.24:1, greater than or equal to about 0.25:1, greater than or equal to about 0.26:1, greater than or equal to about 0.27:1, greater than or equal to about 0.28:1, greater than or equal to about 0.29:1, greater than or equal to about 0.3:1, greater than or equal to about 0.31:1, greater than or equal to about 0.32:1, greater than or equal to about 0.33:1, greater than or equal to about 0.34:1, greater than or equal to about 0.35:1, greater than or equal to about 0.36:1, greater than or equal to about 0.37:1, greater than or equal to about 0.38:1, greater than or equal to about 0.39:1, greater than or equal to about 0.4:1, greater than or equal to about 0.41:1, greater than or equal to about 0.42:1, greater than or equal to about 0.43:1, greater than or equal to about 0.44:1, greater than or equal to about 0.45:1, greater than or equal to about 0.46:1, greater than or equal to about 0.47:1, greater than or equal to about 0.48:1, greater than or equal to about 0.49:1, or greater than or equal to about 0.50:1.

[0144] In the quantum dots of the embodiments, if present, the molar ratio of gallium, aluminum, lithium, or a combination thereof relative to tellurium may be less than or equal to about 1.5: 1, less than or equal to about 1: 1, less than or equal to about 0.9: 1, less than or equal to about 0.85: 1, less than or equal to about 0.8: 1, less than or equal to about 0.75: 1, less than or equal to about 0.7: 1, less than or equal to about 0.65: 1, less than or equal to about 0.6: 1, or less than or equal to about 0.55: 1. Without wishing to be bound by any theory, the presence of gallium, aluminum, lithium, or a combination thereof may contribute to the enhanced luminescent properties of the core-shell quantum dots.

[0145] The semiconductor nanocrystalline shell may include: zinc; and sulfur, selenium, or a combination thereof. The semiconductor nanocrystalline shell may be ZnSe, ZnS, ZnSeS, or a combination thereof.

[0146] The semiconductor nanocrystal shell may be a multilayer shell comprising a plurality of layers. In the plurality of layers of the shell, adjacent layers may have semiconductor nanocrystal materials of different compositions. The multilayer shell may include a first layer disposed directly on the core and a second layer disposed on or above the first layer. The first layer may include a second semiconductor nanocrystal. The second layer may include a third semiconductor nanocrystal having a composition different from that of the second semiconductor nanocrystal. The second layer may be the outermost layer of the quantum dot. The second semiconductor nanocrystal may include zinc, selenium, and optionally sulfur. In an embodiment, the second semiconductor nanocrystal may not include sulfur. The third semiconductor nanocrystal may include zinc and sulfur. In an embodiment, the third semiconductor nanocrystal may not include selenium. In an embodiment, the first layer may include ZnSe, ZnSeS, ZnS, or a combination thereof. The second layer may consist of ZnS.

[0147] In a multilayer shell, the thickness of each layer can be appropriately selected. The thickness of the layer can be greater than or equal to about 1 monolayer (ML), such as greater than or equal to about 2 ML, greater than or equal to about 3 ML, greater than or equal to about 4 ML, greater than or equal to about 5 ML and less than or equal to about 10 ML, such as less than or equal to about 9 ML, less than or equal to about 8 ML, less than or equal to about 7 ML, less than or equal to about 6 ML, or less than or equal to about 5 ML. The thickness of each layer in the multilayer shell can be selected taking into account the desired composition of the final quantum dot.

[0148] In an embodiment, the shell or the layers in the multi-layer shell may each include a gradient alloy having a composition that changes in a radial direction, such as radially from the core toward the outermost surface of the quantum dot. In an embodiment, the amount of sulfur in the semiconductor nanocrystal shell may increase toward the surface of the quantum dot. For example, in the shell, the amount of sulfur may increase in a direction away from the core, such as radially from the core toward the outermost surface of the quantum dot.

[0149] The core-shell quantum dots of embodiments further include chlorine. In embodiments, the semiconductor nanocrystal shell may include chlorine. In embodiments, the core may or may not include chlorine.

[0150] In the core-shell quantum dots, the presence of chlorine can be determined, for example, by X-ray photoelectron spectroscopy (e.g., Cl2P peak). In the core-shell quantum dots, the molar ratio of chlorine to tellurium (Cl:Te) can be greater than or equal to about 0.001:1, greater than or equal to about 0.005:1, greater than or equal to about 0.01:1, greater than or equal to about 0.05:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, greater than or equal to about 0.3:1, greater than or equal to about 0.35:1, or greater than or equal to about 0.4:1. In the core-shell quantum dots, the molar ratio of chlorine to tellurium (Cl:Te) may be less than or equal to about 7:1, less than or equal to about 6.5:1, less than or equal to about 6:1, less than or equal to about 5.5:1, less than or equal to about 5:1, less than or equal to about 4.5:1, less than or equal to about 4:1, less than or equal to about 3.5:1, less than or equal to about 3:1, less than or equal to about 2.5:1, less than or equal to about 2:1, less than or equal to about 1.9:1, less than or equal to about 1.8:1, less than or equal to about 1.7:1, less than or equal to about 1.8:1, less than or equal to about 1.9:1, less than or equal to about 1.8 ... less than or equal to about 1.6:1, less than or equal to about 1.5:1, less than or equal to about 1.4:1, less than or equal to about 1.3:1, less than or equal to about 1.2:1, less than or equal to about 1.1:1, less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.8:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.5:1, less than or equal to about 0.4:1, less than or equal to about 0.3:1, less than or equal to about 0.2:1, or less than or equal to about 0.1:1.

[0151] The core-shell quantum dots of the embodiment may further include fluorine. In the quantum dots, the amount of fluorine may be greater than or equal to about 0.01%, greater than or equal to about 0.02%, greater than or equal to about 0.03%, greater than or equal to about 0.04%, greater than or equal to about 0.05%, greater than or equal to about 0.1% and less than or equal to about 1%, less than or equal to about 0.9%, less than or equal to about 0.8%, less than or equal to about 0.7%, less than or equal to about 0.6%, less than or equal to about 0.5%, less than or equal to about 0.4%, less than or equal to about 0.3%, less than or equal to about 0.2%, less than or equal to about 0.1%, less than or equal to about 0.05%, or less than or equal to about 0.04%, based on the amount of zinc (molar number).

[0152] ZnTe-based core (or ZnTe-based x Se (1-x)An alloy core) can provide quantum dots that can emit light of a desired wavelength, for example, less than or equal to about 600 nm, or less than or equal to about 580 nm and greater than or equal to about 490 nm, or greater than or equal to about 500 nm, even without including toxic heavy metals.

[0153] However, according to the research of the present inventors, the shell formation on such a core may not provide the final core-shell quantum dots with the desired luminescent properties such as luminescent wavelength and luminescent efficiency (particularly, when the core has a large amount of tellurium). Without wishing to be bound by any theory, the II-VI group compound-based core including tellurium may have poor oxidative stability, and during the shell formation, oxidation of tellurium may occur, and the half width may increase and the luminescent efficiency may decrease. In addition, the present inventors have also found that when a core including a predetermined amount of tellurium (for example, wherein ZnTe x Se 1-x When forming a shell on a core having a (x greater than or equal to about 0.4), it may be difficult to achieve a uniform shell coating (coating), and the resulting shell may have a multi-legged shape, for example, when growth toward the polar face (111) becomes dominant. Quantum dots with non-uniform shell coatings may have an increased number of surface traps and irregular shapes.

[0154] The present inventors have discovered that by adding chlorine during quantum dot synthesis (eg, during shell formation), chloride can aid in polar face passivation, reduce face selectivity in shell growth, and promote uniformly shaped shell growth.

[0155] Chlorine added during shell growth can, for example, effectively suppress the aforementioned oxidation phenomenon caused by tellurium included in the core. The core-shell quantum dots of the embodiment include chlorine, and when the core-shell quantum dots have the desired thickness of the shell as formed, the particle morphology can be well controlled and the resulting quantum dots can maintain the desired polygonal shape. Therefore, the core-shell quantum dots of the embodiment can have the desired solidity and roundness values ​​as described herein, and the controlled shape of the core-shell quantum dots can also contribute to the improvement of quantum dot properties (e.g., reduction in FWHM).

[0156] In embodiments, when the tellurium included in the core increases, the improvement in luminescence properties due to the addition of chlorine can be more significant. As the amount of tellurium increases, the resulting core-shell quantum dots can suffer from a deterioration in luminescence properties (e.g., quantum efficiency), for example, the QY of the core-shell quantum dots decreases by about 10%. When the core includes an increased amount of tellurium (e.g., in ZnTe x Se 1-xIn the case of Zn chalcogenide shells, when x = 0.4 or greater or about 0.6 or greater), the use of a chlorine compound during the formation of the Zn chalcogenide shell can provide a significant increase (e.g., a two-fold or three-fold increase) in the luminescent properties (e.g., quantum efficiency) of the final core-shell quantum dots. The quantum dots thus prepared may include a larger amount of tellurium and exhibit a QY of greater than or equal to about 15%, such as greater than or equal to about 20%, or greater than or equal to about 25%.

[0157] The core-shell quantum dots (or a group thereof) may have a particle (average) size of greater than or equal to about 2 nm, greater than or equal to about 3 nm, greater than or equal to about 4 nm, greater than or equal to about 5 nm, greater than or equal to about 6 nm, greater than or equal to about 7 nm, greater than or equal to about 7.5 nm, greater than or equal to about 8 nm, greater than or equal to about 8.5 nm, greater than or equal to about 9 nm, greater than or equal to about 9.5 nm, or greater than or equal to about 10 nm. The size (or average size) of the cadmium-free quantum dots (or a population thereof) may be less than or equal to about 50 nm, e.g., less than or equal to about 45 nm, less than or equal to about 40 nm, less than or equal to about 35 nm, less than or equal to about 30 nm, less than or equal to about 25 nm, less than or equal to about 24 nm, less than or equal to about 23 nm, less than or equal to about 22 nm, less than or equal to about 21 nm, less than or equal to about 20 nm, less than or equal to about 19 nm, less than or equal to about 18 nm, less than or equal to about 17 nm, less than or equal to about 16 nm, less than or equal to about 15 nm, less than or equal to about 14 nm, less than or equal to about 13 nm, less than or equal to about 12 nm, less than or equal to about 11 nm, less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, less than or equal to about 7 nm, less than or equal to about 6 nm, less than or equal to about 5.5 nm, or less than or equal to about 5 nm. As used herein, the size of a quantum dot may refer to a diameter or equivalent diameter obtained from a two-dimensional image analyzed by electron microscopy (e.g., under the assumption of a circle). As used herein, "size" may refer to the size of a single quantum dot or the (e.g., mean or median) average of a plurality of quantum dots or a group of quantum dots. The size of a quantum dot can be determined by using the results (e.g., images) of (transmission) electron microscopy analysis and any commercially available image analysis computer program (e.g., Image J).

[0158] In the quantum dots of the embodiments, the size (or average size) of the core may be greater than or equal to about 1 nm, for example, greater than or equal to about 2 nm, greater than or equal to about 2.5 nm, greater than or equal to about 3 nm, greater than or equal to about 3.5 nm, greater than or equal to about 4 nm, or greater than or equal to about 4.5 nm. The size (or average size) of the core may be less than or equal to about 7 nm, less than or equal to about 6 nm, less than or equal to about 5 nm, less than or equal to about 4 nm, less than or equal to about 3 nm, or less than or equal to about 2 nm.

[0159] The quantum dots may constitute a group of quantum dots. In an embodiment, for example, by the method of the embodiment as described in detail herein, the quantum dots may present a controlled and improved final morphology, and the quantum dot group of the embodiment may present an increased average solidity, average roundness, or a value of a combination thereof. As used herein, average may refer to mean average or median average. The quantum dot group of the embodiment may have an average roundness greater than or equal to about 0.70, greater than or equal to about 0.71, greater than or equal to about 0.72, greater than or equal to about 0.73, greater than or equal to about 0.74, greater than or equal to about 0.75, greater than or equal to about 0.76, greater than or equal to about 0.77, greater than or equal to about 0.78, greater than or equal to about 0.79, greater than or equal to about 0.8, or greater than or equal to about 0.81. The quantum dot group of the embodiment may have an average solidity greater than or equal to about 0.7, greater than or equal to about 0.75, greater than or equal to about 0.8, greater than or equal to about 0.85, or greater than or equal to about 0.9. The quantum dot population can have such controlled shape parameters, which can indicate that uniform shell growth and core passivation can be achieved.

[0160] The population of the aforementioned quantum dots may have a standard deviation of the size of less than or equal to about 18%, less than or equal to about 17%, less than or equal to about 16%, less than or equal to about 15%, less than or equal to about 14%, less than or equal to about 13%, less than or equal to about 12%, or less than or equal to about 11% of the average size of the quantum dots. The population of the aforementioned quantum dots may have a standard deviation of the size of greater than or equal to about 8%, greater than or equal to about 9%, or greater than or equal to about 10% of the average size of the quantum dots.

[0161] The quantum dots of the embodiment are based on the composition of Zn, Te and Se, and have the aforementioned characteristics, for example, having a relatively wide band gap and a relatively narrow, for example, small Bohr radius, for example, compared with cadmium-based quantum dots or quantum dots based on group III-V compounds (e.g., InP). Without wishing to be bound by any theory, in the case of the quantum dots of the aforementioned embodiment, it is understood that the variable width of the band gap of the quantum dots of the embodiment relative to its size variation may be relatively small compared with cadmium-based quantum dots or group III-V compound-based quantum dots (e.g., InP). Therefore, it is believed that in the case of the quantum dots of the embodiment, the size range that enables the quantum dots to have a band gap that emits green light is wider than the size range that enables cadmium-based quantum dots and group III-V compound-based quantum dots (e.g., InP) to have a band gap that emits green light, and the cadmium-free quantum dots of the embodiment may have a narrower FWHM than cadmium-based quantum dots and group III-V compound-based quantum dots (e.g., InP). Conventional QDs including ZnTeSe that emit green light may have a luminous efficiency of less than about 1%. In an embodiment, a quantum dot is provided that includes a core of a ZnTeSe-based alloy and emits light having a wavelength greater than about 470 nm and less than or equal to about 560 nm with a predetermined efficiency, such as a luminous efficiency greater than or equal to about 10% or greater than or equal to about 15%.

[0162] Surprisingly, the inventors have found that by adopting the method as described in detail herein, the uniformity and roundness of the ZnTeSe core (or its group) can be greatly improved, and when a shell of ZnSe, ZnSeS, ZnS, or ZnSe / ZnS is coated on the ZnTeSe core having the aforementioned characteristics, the resulting quantum dots can exhibit greatly improved, for example, improved luminous efficiency and reduced FWHM. The quantum dots of the embodiments can emit light of a desired wavelength range with improved quantum efficiency and reduced FWHM.

[0163] In an embodiment, the ultraviolet-visible (UV-Vis) absorption spectrum of the (core or core-shell) quantum dot may include a valley that can be relatively clearly noticed. In the ultraviolet-visible absorption spectrum, the quantum dot of the embodiment may have a valley adjacent to the first absorption peak or within a range of about 450 nm or more (or about 440 nm or more, about 430 nm or more, about 420 nm or more, about 410 nm or more, about 400 nm or more) up to the wavelength of the first absorption peak.

[0164] The quantum dots of the embodiment may exhibit a valley depth of at least a predetermined value. In the ultraviolet-visible absorption spectrum of the quantum dots of the embodiment, the valley or its lowest point may appear at a wavelength smaller than, for example, a shorter wavelength than the wavelength of the first absorption peak. In the ultraviolet-visible absorption spectrum of the quantum dots, the intensity of the first absorption peak may be greater than the intensity at the lowest point of the valley adjacent thereto.

[0165] Without being bound by any theory, it is believed that in the ultraviolet-visible (UV-Vis) absorption spectrum, the presence of valleys or valley depths may represent the size uniformity of the quantum dots (or cores) or the uniformity of the shell coating of the quantum dots. The significant valley depth of the core-shell quantum dots or core quantum dots may indicate that the (core-shell) quantum dots may have improved size distribution, improved coating quality, or a combination thereof, and may provide a narrower FWHM and increased luminous efficiency.

[0166] In the quantum dots of the embodiments, the valley depth defined herein may be greater than or equal to about 0.01, e.g., greater than or equal to about 0.02, greater than or equal to about 0.03, greater than or equal to about 0.04, greater than or equal to about 0.05, greater than or equal to about 0.06, greater than or equal to about 0.07, greater than or equal to about 0.08, greater than or equal to about 0.09, or greater than or equal to about 0.1.

[0167] The first absorption peak of the quantum dot may exist in a wavelength range greater than or equal to about 410 nm, for example, greater than or equal to about 420 nm, greater than or equal to about 430 nm, greater than or equal to about 440 nm, greater than or equal to about 450 nm, greater than or equal to about 460 nm, greater than or equal to about 465 nm, greater than or equal to about 470 nm, greater than or equal to about 475 nm, or greater than or equal to about 480 nm.

[0168] The lowest point of the valley of the quantum dot may exist in a wavelength range of greater than or equal to about 410 nm, for example, greater than or equal to about 420 nm, greater than or equal to about 430 nm, greater than or equal to about 440 nm, greater than or equal to about 450 nm, greater than or equal to about 460 nm, greater than or equal to about 465 nm, greater than or equal to about 470 nm, greater than or equal to about 475 nm, or greater than or equal to about 480 nm.

[0169] The first absorption peak of the quantum dot may exist in a wavelength range of less than or equal to about 530 nm, less than or equal to about 525 nm, less than or equal to about 520 nm, less than or equal to about 515 nm, less than or equal to about 510 nm, less than or equal to about 505 nm, less than or equal to about 500 nm, less than or equal to about 495 nm, less than or equal to about 490 nm, less than or equal to about 485 nm, less than or equal to about 480 nm, less than or equal to about 475 nm, less than or equal to about 465 nm, less than or equal to about 460 nm, less than or equal to about 455 nm, less than or equal to about 450 nm, or less than or equal to about 445 nm.

[0170] The lowest point of the valley of the quantum dot may exist within a wavelength range of less than or equal to about 530 nm, less than or equal to about 525 nm, less than or equal to about 520 nm, less than or equal to about 515 nm, less than or equal to about less than or equal to about 510 nm, less than or equal to about 505 nm, less than or equal to about 500 nm, less than or equal to about 495 nm, less than or equal to about 490 nm, less than or equal to about 485 nm, less than or equal to about 480 nm, less than or equal to about 475 nm, less than or equal to about 465 nm, less than or equal to about 460 nm, less than or equal to about 455 nm, less than or equal to about 450 nm, or less than or equal to about 445 nm.

[0171] Compared to other quantum dots based on Zn, Te and Se, the quantum dots of the embodiments can exhibit improved quantum efficiency, for example, a quantum efficiency of about 10% or more. The quantum dots of the embodiments can emit light with a quantum efficiency of about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 35%, about 40%, about 45%, or about 50%.

[0172] The maximum photoluminescence peak wavelength of the quantum dot may exist in a range of greater than about 470 nm, such as greater than or equal to about 471 nm, greater than or equal to about 472 nm, greater than or equal to about 473 nm, greater than or equal to about 474 nm, greater than or equal to about 475 nm, greater than or equal to about 476 nm, greater than or equal to about 477 nm, greater than or equal to about 478 nm, greater than or equal to about 479 nm, greater than or equal to about 480 nm, greater than or equal to about 485 nm, greater than or equal to about 490 nm, greater than or equal to about 495 nm, greater than or equal to about 500 nm, greater than or equal to about 505 nm, greater than or equal to about 510 nm, greater than or equal to about 515 nm, or greater than or equal to about 520 nm. The quantum dot may have a maximum PL peak wavelength less than or equal to about 550 nm, such as less than or equal to about 540 nm, or less than or equal to about 535 nm. The quantum dot of an embodiment may emit green light. The green light may have a maximum light emission peak wavelength of about 500 nm to about 560 nm (eg, greater than or equal to about 515 nm and less than or equal to about 535 nm).

[0173] Embodiment (cadmium-free) quantum dots may have a FWHM of less than about 50 nm, less than or equal to about 45 nm, less than or equal to about 40 nm, less than or equal to about 39 nm, less than or equal to about 38 nm, less than or equal to about 37 nm, less than or equal to about 36 nm, less than or equal to about 35 nm, less than or equal to about 34 nm, less than or equal to about 33 nm, less than or equal to about 32 nm, less than or equal to about 31 nm, less than or equal to about 30 nm, less than or equal to about 29 nm, less than or equal to about 28 nm, less than or equal to about 27 nm, less than or equal to about 26 nm, or less than or equal to about 25 nm.

[0174] The quantum dots may include organic ligands, for example, on their surface. The organic ligands may include RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, RH 2 PO, R 2 HPO, R 3 PO, RH 2 P.R 2 HP, R 3 P, ROH, RCOOR', RPO(OH) 2 , RHPOOH, R 2POOH, polymeric organic ligands, or combinations thereof, wherein R and R' are the same or different and are independently C1-C40 (e.g., C3-C30 or C6-C24) substituted or unsubstituted aliphatic hydrocarbon (e.g., alkyl, alkenyl, or alkynyl) groups or C6-C40 substituted or unsubstituted aromatic hydrocarbon groups, or combinations thereof. Two or more different organic ligands may be used.

[0175] The organic ligand can be coordinated to, for example, the surface of the quantum dot to help the nanocrystals to be well dispersed in the solution. Examples of the organic ligand can include methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexadecyl mercaptan, octadecyl mercaptan, or benzyl mercaptan; methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine; formic acid, acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, or benzoic acid; phosphines such as substituted or unsubstituted methyl phosphine (e.g., trimethyl phosphine, methyl diphenyl phosphine, etc.), substituted or unsubstituted ethyl phosphine (e.g., triethyl phosphine, ethyl diphenyl phosphine, etc.), substituted or unsubstituted propyl phosphine, substituted or unsubstituted butyl phosphine, substituted or unsubstituted pentyl phosphine, or substituted or unsubstituted octyl phosphine (e.g., trioctyl phosphine (TOP)); phosphine oxides such as substituted or unsubstituted methyl phosphine oxide (e.g., trimethyl phosphine, methyl diphenyl phosphine, etc.), substituted or unsubstituted ethyl phosphine (e.g., triethyl phosphine, ethyl diphenyl phosphine, etc.), substituted or unsubstituted propyl phosphine, substituted or unsubstituted butyl phosphine, substituted or unsubstituted pentyl phosphine, or substituted or unsubstituted octyl phosphine (e.g., trioctyl phosphine (TOP)); phosphine oxide, methyl diphenyl phosphine oxide, etc.), substituted or unsubstituted ethyl phosphine oxide (for example, triethyl phosphine oxide, ethyl diphenyl phosphine oxide, etc.), substituted or unsubstituted propyl phosphine oxide, substituted or unsubstituted butyl phosphine oxide, or substituted or unsubstituted octyl phosphine oxide (for example, trioctyl phosphine oxide (TOPO)); diphenylphosphine, diphenylphosphine oxide, triphenylphosphine, or triphenylphosphine oxide; mono- or di-(C5-C20 alkyl) phosphinic acid such as mono- or di-hexylphosphinic acid, mono- or di-octylphosphinic acid, mono- or di-dodecylphosphinic acid, mono- or di-tetradecylphosphinic acid, mono- or di-hexadecylphosphinic acid, mono- or di-octadecylphosphinic acid, or a combination thereof; C5-C20 alkyl phosphinic acid, C5-C20 alkyl phosphonic acid such as hexylphosphonic acid, octylphosphonic acid, dodecylphosphonic acid, tetradecylphosphonic acid, hexadecylphosphonic acid, octadecylphosphonic acid, or a combination thereof; or a combination thereof, etc., but are not limited thereto. Two or more different organic ligand compounds may be used.

[0176] In an embodiment, the organic ligand compound may be RCOOH and an amine (eg, RNH 2 , R 2 NH, R 3In an embodiment, the organic ligand may not include an organic compound having a thiol moiety and an amino group, a carboxylic acid group, or a combination thereof.

[0177] In an embodiment, the organic ligand may not include a multifunctional organic compound having a thiol moiety and an amino group, a carboxylic acid, or a combination thereof. In an embodiment, the organic ligand may not include a glutathione compound. The quantum dot may be water-insoluble.

[0178] When dispersed in water, the quantum dots may exhibit, for example, an average particle size of greater than or equal to about 300 nm, greater than or equal to about 400 nm, greater than or equal to about 500 nm, or greater than or equal to about 900 nm as determined by dynamic light scattering (DLS) analysis. When dispersed in an organic solvent (e.g., toluene, octane, etc.), the quantum dots may be configured to form an organic solution having an average particle size of less than or equal to about 500 nm, less than or equal to about 400 nm, less than or equal to about 300 nm, less than or equal to about 200 nm, less than or equal to about 100 nm, or less than or equal to about 90 nm as determined by DLS analysis. Examples of the organic solvents are described herein.

[0179] In an embodiment, a method of making the core-shell quantum dots comprises:

[0180] preparing a core particle including the core;

[0181] reacting a zinc precursor with a selenium precursor, a sulfur precursor, or a combination thereof at a shell forming temperature in the presence of the core particle and a shell forming organic ligand in a first organic solvent to form a semiconductor nanocrystal shell comprising zinc and selenium, sulfur, or a combination thereof on the surface of the core,

[0182] The preparation of the core includes

[0183] preparing a zinc precursor organic solution comprising a zinc precursor and a first organic ligand in a first organic solvent; and

[0184] while heating the zinc precursor organic solution at a first reaction temperature, adding a selenium precursor, a tellurium precursor, a hydride compound, and a second organic ligand, such as at least one second organic ligand, to the zinc precursor organic solution, and

[0185] The method further comprises adding a chlorine precursor to the reaction system during core preparation, during shell formation, or during core preparation and during shell formation. The chlorine precursor can be prepared by dissolving a chlorine compound in a fourth organic solvent. In the method of an embodiment, the chlorine precursor can be added to the reaction system during shell formation.

[0186] The details of the composition of the core-shell quantum dots and the core and the semiconductor nanocrystal shell are the same as those described herein. The synthesized core can be separated from the reaction system (e.g., before the shell is synthesized) (e.g., by adding a non-solvent). The details of the non-solvent are described in detail herein.

[0187] As described herein, the method using the embodiments can provide quantum dots with relatively improved luminescent properties when, for example, a shell of the quantum dots is formed on a ZnTeSe alloy core including an increased amount of tellurium. It has been widely known in the past that core-shell quantum dots based on ZnTeSe alloy cores can hardly exhibit the desired luminescent properties. For example, quantum dots obtained by forming a shell on a ZnTeSe alloy core tend to exhibit a significantly widened FWHM and have a luminescent efficiency as high as about 1%. Without wishing to be bound by any theory, as described herein, it is believed that the deterioration of the luminescent efficiency can be attributed to the significant oxidation sensitivity of the ZnTeSe alloy core.

[0188] Without wishing to be bound by any theory, it is believed that in the method of the embodiment, the chlorine precursor is present during the formation of the core-shell quantum dots (e.g., during the formation of the shell) to effectively prevent oxidation of tellurium during high temperature reactions, and when the temperature of shell formation is increased to a higher level, the reduction in PLQY can be suppressed. The increase in the thickness of the shell grown on the ZnTeSe alloy core can result in a significant change in the particle morphology and a final quantum dot having a multi-legged shape. In contrast, according to the method of the embodiment, the presence of chlorine (e.g., in a predetermined amount) can help produce core-shell quantum dots having a polygonal shape, and the core-shell quantum dots prepared thereby can have the aforementioned shape characteristics (e.g., average solidity, roundness, or a combination thereof as described herein).

[0189] In an embodiment, the tellurium precursor used during the core synthesis may include tellurium dispersed in a second organic solvent, and the concentration of tellurium in the tellurium precursor may be greater than about 0.1 M, such as greater than or equal to about 0.5 M, greater than or equal to about 1 M, greater than or equal to about 1.5 M, greater than or equal to about 2 M, or greater than or equal to about 2.5 M. The concentration of tellurium may be less than or equal to about 10 M, less than or equal to about 5 M, or less than or equal to about 4 M.

[0190] The inventors have also found that using more than a predetermined amount of Te precursor (e.g., Te / TOP) to synthesize the core can result in a non-uniform particle size distribution and a non-spherical core of the synthesized core. Without wishing to be bound by any theory, the reactivity of tellurium in the reaction system is related to the quality of the core as prepared. The tellurium precursor may not have a sufficiently strong bond between the chalcogen and the solvent (e.g., TOP). For example, at room temperature, a solvent (e.g., free TOP) added in a free state may form a Te-TOP bond in the precursor, and unlike other chalcogen precursors, the tellurium precursor may have only a weak bond (e.g., a bond at the solvation level) with the solvent. In the method of the embodiment, reducing, for example, reducing the ratio of the solvent to tellurium such as a molar ratio or a weight ratio (i.e., increasing the concentration of tellurium in the precursor) may increase the reactivity of tellurium. Such an increased reactivity of tellurium in combination with the use of the hydride compound and the second organic ligand may result in an increase in the valley depth of the core. The increased valley depth of the core may indicate that a given core has improved quality (e.g., uniform surface and uniform size distribution). In addition, increasing the concentration of the metal precursor in the reaction system may result in surface coverage of the organic ligand, and the resulting quantum dots may exhibit, for example, further improved valley depth. Thus, the core prepared by the method of the embodiment may include an increased amount of organic material, for example, as determined by thermogravimetric analysis.

[0191] Therefore, the core prepared according to the method of the embodiment can have improved uniformity of size distribution together with improved roundness and more uniform surface coverage. Without wishing to be bound by any theory, when a shell is formed on the aforementioned core, the surface selectivity for shell formation can be reduced and thus a coating layer with improved quality can be achieved. Therefore, the resulting quantum dots including a core-shell structure based on a ZnTeSe core can exhibit enhanced, for example, improved luminescent properties (e.g., improved quantum efficiency and improved FWHM).

[0192] In an embodiment, during the synthesis of the core, the selenium precursor, tellurium precursor, metal hydride compound, and second organic ligand may be mixed together to form a single stock solution at a temperature of less than about 80° C., such as less than or equal to about 75° C., less than or equal to about 70° C., less than or equal to about 65° C., less than or equal to about 60° C., less than or equal to about 55° C., less than or equal to about 50° C., or less than or equal to about 45° C., before being added to the zinc precursor organic solution. The temperature may be greater than or equal to about 10° C., greater than or equal to about 20° C., or, for example, about room temperature.

[0193] The second organic ligand may be an aliphatic organic amine compound or a combination thereof. The metal hydride compound may include lithium, aluminum, or a combination thereof. The metal hydride compound may include an aluminum hydride compound, a lithium hydride compound, or a combination thereof. The metal hydride compound may include an organic metal hydride compound (e.g., having a hydrocarbon group, e.g., at least one hydrocarbon group), an inorganic metal hydride compound, or a combination thereof. The metal hydride compound may include an alkyl lithium hydride (e.g., a dialkyl lithium borohydride, wherein each alkyl group may have 1-6 carbon atoms), a lithium aluminum hydride compound, or a combination thereof.

[0194] The amount of the metal hydride is not particularly limited and can be appropriately selected. The amount of the metal hydride may be greater than or equal to about 0.01 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.5 mole, or greater than or equal to about 1 mole per 1 mole of antimony. The amount of the metal hydride may be less than or equal to about 10 moles, less than or equal to about 5 moles, or less than or equal to about 3 moles per 1 mole of antimony.

[0195] During preparation of the core, the molar ratio of tellurium to selenium (Te:Se) introduced into the reaction system may be greater than about 0.25:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.7:1, greater than or equal to about 0.9:1, greater than or equal to about 1:1, greater than or equal to about 1.1:1, greater than or equal to about 1.2:1, greater than or equal to about 1.3:1, greater than or equal to about 1.4:1, greater than or equal to about 1.5:1, greater than or equal to about 1.6:1, greater than or equal to about 1.7:1, greater than or equal to about 1.8:1, greater than or equal to about 1.9:1, greater than or equal to about 2:1, or greater than or equal to about 2.5:1.

[0196] During preparation of the core, the molar ratio of tellurium to selenium (Te:Se) introduced into the reaction system may be less than or equal to about 10:1, less than or equal to about 9:1, less than or equal to about 8:1, less than or equal to about 7:1, less than or equal to about 6:1, less than or equal to about 5:1, less than or equal to about 4:1, less than or equal to about 3:1, less than or equal to about 2:1, or less than or equal to about 1.5:1.

[0197] During the preparation of the core, the molar ratio of zinc to tellurium may be appropriately selected in consideration of a desired composition, a precursor, etc. According to an embodiment, during the preparation of the core, the amount of zinc relative to one mole of tellurium may be greater than or equal to about 1 mole, greater than or equal to about 2 moles, greater than or equal to about 3 moles, greater than or equal to about 4 moles, or greater than or equal to about 5 moles. According to an embodiment, during the preparation of the core, the amount of zinc relative to one mole of tellurium may be less than or equal to about 20 moles, less than or equal to about 15 moles, less than or equal to about 10 moles, less than or equal to about 9 moles, less than or equal to about 8 moles, less than or equal to about 7 moles, less than or equal to about 6 moles, less than or equal to about 5 moles, less than or equal to about 4 moles, less than or equal to about 3 moles, or less than or equal to about 2 moles.

[0198] In an embodiment, the formation of the shell can be implemented as follows: the shell metal precursor and the organic ligand are heated (or vacuum treated) in an organic solvent at a predetermined temperature (e.g., at a temperature greater than or equal to about 100° C., such as greater than or equal to about 120° C.) under vacuum, the atmosphere of the reaction system is changed to an inert gas, and it is heated at a predetermined reaction temperature.

[0199] The core and non-metallic shell precursors (eg, sulfur and selenium precursors) may be added to a (heated) reaction system to carry out the reaction. The shell precursors may be injected simultaneously or sequentially during the reaction in consideration of the desired shell composition.

[0200] A shell having a desired composition (eg, a gradient composition or a multi-layered composition) can be formed.

[0201] In an embodiment, the formation of the semiconductor nanocrystal shell may include reacting the zinc precursor with the selenium precursor, the sulfur precursor, or a combination thereof. In an embodiment, the formation of the semiconductor nanocrystal shell may include reacting the zinc precursor with the selenium precursor, and then reacting the zinc precursor with the sulfur precursor. For example, in an embodiment, a zinc precursor may react with a selenium precursor to form a first layer including zinc and selenium, and then react with a sulfur precursor to form a second layer including zinc and sulfur. In an embodiment, a zinc precursor may react with the selenium and sulfur precursors to form a semiconductor nanocrystal shell including zinc, selenium and sulfur (e.g., ZnSeS).

[0202] The chlorine precursor can be easily prepared by dissolving the chlorine compound in a fourth organic solvent. The fourth organic solvent may be miscible with the first organic solvent, the second organic solvent, the third organic solvent, or a combination thereof. In an embodiment, the fourth organic solvent may have a boiling point that is at least 10°C, such as at least 50°C, or at least 100°C less than the shell formation temperature. In an embodiment, the fourth organic solvent may include a C2-C30 ketone solvent (e.g., acetone), a C1-C30 alcohol solvent such as ethanol, methanol, etc., a C1-C40 alkylphosphine solvent such as TOP, or a combination thereof.

[0203] The chlorine compound may include a chloride of a polyvalent metal (e.g., zinc, gallium, aluminum, or indium). The chlorine compound may include zinc chloride, gallium chloride, aluminum chloride, indium chloride, or a combination thereof. The polyvalent metal may be the same as the metal included in the semiconductor nanocrystal shell. In the chlorine precursor, the concentration of the chlorine compound may be determined by considering the type of the chlorine compound and the fourth organic solvent and is not particularly limited. In an embodiment, the concentration of the chlorine compound in the chlorine precursor may be greater than or equal to about 0.1M, greater than or equal to about 0.2M, greater than or equal to about 0.3M, greater than or equal to about 0.4M, or greater than or equal to about 0.5M and less than or equal to about 10M, less than or equal to about 9M, less than or equal to about 8M, less than or equal to about 7M, less than or equal to about 6M, less than or equal to about 5M, less than or equal to about 4M, less than or equal to about 3M, less than or equal to about 2M, less than or equal to about 1M.

[0204] The method may further include adding a fluorine compound to the reaction system.

[0205] Based on one mole of sulfur (or selenium), the amount of the chlorine precursor (or chlorine compound), the amount of the fluorine compound (if used), or the amount of the chlorine precursor (or chlorine compound) and the amount of the fluorine compound may be greater than or equal to about 0.001 mole, greater than or equal to about 0.005 mole, greater than or equal to about 0.01 mole, greater than or equal to about 0.03 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.07 mole, greater than or equal to about 0.09 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.15 mole, greater than or equal to about 0.2 mole, greater than or equal to about 0.25 mole, greater than or equal to about 0.3 mole, or greater than or equal to about 0.35 mole, or greater than or equal to about 0.4 mole.

[0206] Based on one mole of sulfur (or selenium), the amount of the chlorine precursor (or chlorine compound), the amount of the fluorine compound (if used), or the amount of the chlorine precursor (or chlorine compound) and the amount of the fluorine compound may be less than or equal to about 10 moles, less than or equal to about 9 moles, less than or equal to about 8 moles, less than or equal to about 7 moles, less than or equal to about 6 moles, less than or equal to about 5 moles, less than or equal to about 4 moles, less than or equal to about 3 moles, less than or equal to about 2 moles, less than or equal to about 1 mole, less than or equal to about 0.9 moles, less than or equal to about 0.8 moles, less than or equal to about 0.7 moles, less than or equal to about 0.6 moles, less than or equal to about 0.5 moles, less than or equal to about 0.4 moles, less than or equal to about 0.3 moles, less than or equal to about 0.2 moles, less than or equal to about 0.1 moles, or less than or equal to about 0.05 moles.

[0207] In the method, the zinc precursor may include Zn powder, ZnO, an alkylated Zn compound (e.g., C2-C30 alkyl (e.g., dialkyl) zinc such as dimethyl zinc, diethyl zinc), Zn alkoxide (e.g., zinc ethoxide), Zn carboxylate (e.g., zinc acetate or aliphatic zinc carboxylate such as long-chain aliphatic zinc carboxylate such as zinc oleate), Zn nitrate, Zn perchlorate, Zn sulfate, Zn acetylacetonate, Zn halide (e.g., zinc chloride), Zn cyanide, Zn hydroxide, zinc carbonate, zinc peroxide, or a combination thereof. Examples of the zinc precursor may include dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, or a combination thereof.

[0208] The selenium precursor may include selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), selenium-diphenylphosphine (Se-DPP), or a combination thereof, but is not limited thereto.

[0209] The tellurium precursor may include tellurium-trioctylphosphine (Te-TOP), tellurium-tributylphosphine (Te-TBP), tellurium-triphenylphosphine (Te-TPP), tellurium-diphenylphosphine (Te-DPP), or a combination thereof, but is not limited thereto.

[0210] The sulfur precursor may include hexanethiol, octylthiol, decanethiol, dodecanethiol, hexadecylthiol, mercaptopropylsilane, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), sulfur-trioctylamine (S-TOA), sulfur-octadecene (S-ODE), bistrimethylsilyl sulfide, ammonium sulfide, sodium sulfide, or a combination thereof.

[0211] The first organic solvent, the second organic solvent, the third organic solvent, or a combination thereof may be the same as or different from each other. The first organic solvent, the second organic solvent, the third organic solvent, or a combination thereof (hereinafter referred to as the organic solvent) may be a C6-C22 primary amine such as hexadecylamine, a C6-C22 secondary amine such as dioctylamine, a C6-C40 tertiary amine such as trioctylamine, a nitrogen-containing heterocyclic compound such as pyridine, a C6-C40 olefin such as octadecene, a C6-C40 aliphatic hydrocarbon such as hexadecane, octadecane, or squalane, an aromatic hydrocarbon substituted with a C6-C30 alkyl group such as phenyldodecane, phenyltetradecane, or phenylhexadecane, a primary, secondary or tertiary phosphine substituted with a C6-C22 alkyl group such as at least one (e.g., 1, 2 or 3) C6-C22 alkyl group (e.g., trioctylphosphine), a phosphine oxide substituted with a C6-C22 alkyl group such as at least one (e.g., 1, 2 or 3) C6-C22 alkyl group (e.g., trioctylphosphine oxide), a C12-C22 aromatic ether such as phenyl ether or benzyl ether, or a combination thereof.

[0212] The first organic ligand and the second organic ligand may be the same. The first organic ligand and the second organic ligand may be different. The details of the first and second organic ligands and the shell forming organic ligand are the same as those described herein for the organic ligand. In an embodiment, the first organic ligand may include a fatty acid (e.g., including a C5 or larger or C10 or larger aliphatic hydrocarbon group), and the second organic ligand may include a fatty organic (e.g., primary) amine (e.g., including a C10 or larger aliphatic or aromatic hydrocarbon group), an aromatic phosphine compound, or a combination thereof.

[0213] The aliphatic hydrocarbon group may have a carbon number greater than or equal to about 5, greater than or equal to about 10, greater than or equal to about 15, greater than or equal to about 16, greater than or equal to about 17, greater than or equal to about 18, greater than or equal to about 19, or greater than or equal to about 20; less than or equal to about 50, less than or equal to about 40, or less than or equal to about 30; or combinations thereof.

[0214] The amounts of the first organic ligand and the second organic ligand may be selected in consideration of the type of the organic ligand and the type of the precursor.

[0215] The amount of the first organic ligand (or the amount of the second ligand or the amount of the shell-forming organic ligand) relative to 1 mole of the zinc precursor may be greater than or equal to about 0.1 mole, greater than or equal to about 0.2 mole, greater than or equal to about 0.3 mole, greater than or equal to about 0.4 mole, greater than or equal to about 0.5 mole, greater than or equal to about 0.6 mole, greater than or equal to about 0.7 mole, greater than or equal to about 0.8 mole, greater than or equal to about 0.9 mole, greater than or equal to about 1 mole, greater than or equal to about 2 moles, greater than or equal to about 3 moles, greater than or equal to about 4 moles, or greater than or equal to about 5 moles. The amount of the first organic ligand (or the amount of the second ligand or the amount of the shell-forming organic ligand) relative to 1 mole of the zinc precursor may be less than or equal to about 20 moles, less than or equal to about 19 moles, less than or equal to about 18 moles, less than or equal to about 17 moles, less than or equal to about 16 moles, less than or equal to about 15 moles, less than or equal to about 14 moles, less than or equal to about 13 moles, less than or equal to about 12 moles, less than or equal to about 10 moles, less than or equal to about 9 moles, less than or equal to about 8 moles, less than or equal to about 7 moles, less than or equal to about 6 moles, less than or equal to about 5 moles, less than or equal to about 4 moles, less than or equal to about 3 moles, less than or equal to about 2 moles, or less than or equal to about 1 mole.

[0216] The molar ratio between the first organic ligand and the second organic ligand (the first organic ligand: the second organic ligand) may be 1: about 0.1 or greater, 1: about 0.5 or greater, 1: about 0.9 or greater, or 1: about 1 or greater; 1: about 10 or less; 1: about 5 or less, 1: about 2.5 or less, or 1: about 1.5 or less; or a combination thereof.

[0217] In an embodiment, the selenium precursor, tellurium precursor, metal hydride compound may be injected into the zinc precursor organic solution in a mixed state, optionally together with the organic ligand. In an embodiment, the selenium precursor, tellurium precursor, and metal hydride compound may be injected into the zinc precursor organic solution sequentially.

[0218] The reaction temperature for the core formation may be greater than or equal to about 250° C., greater than or equal to about 260° C., greater than or equal to about 270° C., greater than or equal to about 280° C., greater than or equal to about 290° C., or greater than or equal to about 300° C. The reaction temperature for the core formation may be less than or equal to about 350° C., for example, less than or equal to about 340° C., less than or equal to about 330° C., less than or equal to about 320° C., or less than or equal to about 310° C. The reaction time for the core formation is not particularly limited and may be appropriately selected.

[0219] The reaction temperature for the shell formation may be appropriately selected in any suitable range of about 200° C. or more, for example, about 210° C. or more, about 220° C. or more, about 230° C. or more, about 240° C. or more, about 250° C. or more, about 260° C. or more, about 270° C. or more, about 280° C. or more, or about 290° C. or more and about 340° C. or less, for example, about 325° C. or less. The reaction time for the shell formation may be appropriately selected in consideration of the desired shell composition.

[0220] In the reaction system for forming the core and the reaction system for forming the shell, the amount of each precursor and its concentration can be selected taking into account the desired composition of the core and the shell, the reactivity between the core and the shell precursors, etc. In an embodiment, the ratio between the precursors can be controlled taking into account the desired composition of the final quantum dots (e.g., the ratio between elements such as Zn, S, Se, Te, or a combination thereof, such as a molar ratio). The composition of the final quantum dots can be determined by appropriate analytical tools such as inductively coupled plasma atomic emission spectroscopy.

[0221] After the formation of the core, the shell or its combination, a non-solvent is added to the reaction product, and the nano-crystal particles of for example combination with the ligand compound coordination can be separated. The non-solvent can be a polar solvent miscible with the solvent used in the core formation reaction, the shell formation reaction or its combination and the nano-crystals produced can not be dispersed therein. The non-solvent can be selected in consideration of the solvent used in the reaction, and can be for example acetone, ethanol, butanol, isopropanol, ethylene glycol, water, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), diethyl ether, formaldehyde, acetaldehyde, a solvent with a solubility parameter similar to the aforementioned non-solvent or its combination. The separation of the nano-crystal particles can involve centrifugation, sedimentation, chromatography or distillation. If desired, the separated nano-crystal particles can be added to a washing (or dispersion) solvent and washing (or dispersion).

[0222] The type of the washing (or dispersing) solvent is not particularly limited, and a solvent having a solubility parameter similar to that of the ligand may be used, and examples thereof may include hexane, heptane, octane, chloroform, toluene, benzene, and the like.

[0223] In an embodiment, the quantum dot composition includes: the aforementioned (e.g., multiple) core-shell quantum dots (hereinafter, may be referred to as quantum dots for short); and a (photo)polymerizable monomer optionally having a carbon-carbon double bond, such as at least one carbon-carbon double bond. The composition may further include an organic solvent, a liquid carrier (vehicle), a dispersant (e.g., a binder monomer or polymer), a (photo)initiator; or a combination thereof. The binder monomer or polymer may include a carboxylic acid group.

[0224] The amount of the quantum dots in the composition (or the composite as described herein) can be appropriately adjusted taking into account the desired end use (e.g., photoluminescent color filter, etc.) and ingredients of the composition (or the composite). In an embodiment, the amount of the quantum dots can be greater than or equal to about 1 weight percent (wt%), such as greater than or equal to about 2 wt%, greater than or equal to about 3 wt%, greater than or equal to about 4 wt%, greater than or equal to about 5 wt%, greater than or equal to about 6 wt%, greater than or equal to about 7 wt%, greater than or equal to about 8 wt%, greater than or equal to about 9 wt%, greater than or equal to about 10 wt%, greater than or equal to about 15 wt%, greater than or equal to about 20 wt%, greater than or equal to about 25 wt%, greater than or equal to about 30 wt%, greater than or equal to about 35 wt%, or greater than or equal to about 40 wt%, based on the total solid content of the composition. The amount of the quantum dots may be less than or equal to about 70 wt %, e.g., less than or equal to about 65 wt %, less than or equal to about 60 wt %, less than or equal to about 55 wt %, or less than or equal to about 50 wt %, based on the total solids content of the composition.

[0225] The composition according to the embodiment can be used to manufacture a quantum dot polymer composite pattern. The composition according to the embodiment can be a photoresist composition containing quantum dots to which a photolithography method can be applied. The composition according to the embodiment can be an ink composition that can provide a pattern by printing (e.g., a droplet discharge method such as inkjet printing).

[0226] The binder polymer may include a copolymer of a monomer mixture including: a first monomer including a carboxylic acid group and a carbon-carbon double bond, a second monomer including a carbon-carbon double bond and a hydrophobic portion and not including a carboxylic acid group, and optionally a third monomer including a carbon-carbon double bond and a hydrophilic portion and not including a carboxylic acid group;

[0227] A polymer containing a polyaromatic ring (hereinafter, cardo binder) having a backbone structure in which two aromatic rings are bonded to a quaternary carbon atom which is a constituent atom of another cyclic part in the main chain and including a carboxylic acid group (—COOH); or

[0228] Its combination.

[0229] Details of the quantum dot composition (eg, photosensitive composition) may be found in US-2017-0059988-A1, the entire contents of which are incorporated herein by reference.

[0230] In an embodiment, an electronic device may include the quantum dots. The electronic device may include a display device, a light emitting diode (LED), an organic light emitting diode (OLED), a QD LED, a sensor, a solar cell, an imaging sensor, or a liquid crystal display (LCD), but is not limited thereto.

[0231] In an embodiment, the electronic device may be a photoluminescent device (e.g., a lighting system such as a quantum dot sheet, a quantum dot rail, a backlight unit, etc., or a liquid crystal display) or an electroluminescent device (e.g., a QD light emitting diode (LED)). In a non-limiting example, the electronic device may include a quantum dot sheet, and the aforementioned quantum dots may be included in the QD sheet, for example, as a semiconductor nanocrystal polymer composite.

[0232] In an embodiment, a display device includes a light emitting element (e.g., a photoluminescent element), and the light emitting element includes the aforementioned quantum dot complex. The display device may further include a light source configured to provide incident light to the light emitting element. The incident light may have a (photoluminescence) peak wavelength greater than or equal to about 440 nm, for example, greater than or equal to about 450 nm and less than or equal to about 560 nm, less than or equal to about 500 nm, less than or equal to about 470 nm, or less than or equal to about 460 nm.

[0233] In an embodiment, the light emitting element may include a sheet of the quantum dot polymer composite. The display device may further include a liquid crystal panel, and the sheet of the quantum dot polymer composite may be disposed between the light source and the liquid crystal panel. Figure 3 Shows an exploded view of the display device. Figure 3 The display device may have a structure in which a reflector, a light guide plate (LGP) and a blue LED light source (blue-LED), a quantum dot polymer composite sheet (QD sheet), and various optical films such as a prism, a double brightness enhancement film (DBEF), etc. are stacked, and a liquid crystal panel is disposed thereon.

[0234] In an embodiment, the display device may include a stacked structure including a (e.g., transparent) substrate and a light-emitting layer (e.g., a photoluminescent layer) disposed on the substrate as a light-emitting element. In the stacked structure, the light-emitting layer includes a pattern of the quantum dot polymer composite, and the pattern may include a repeating segment configured to emit light of a predetermined wavelength, for example, at least one repeating segment. The pattern of the quantum dot polymer composite may include a first repeating segment that can emit a first light, a second repeating segment that can emit a second light, or a combination thereof.

[0235] The first light and the second light have different maximum photoluminescence peak wavelengths in the photoluminescence spectrum. In an embodiment, the first light may be red light (R) having a maximum photoluminescence peak wavelength of about 600 nm to about 650 nm (e.g., about 620 nm to about 650 nm), and the second light may be green light (G) having a maximum photoluminescence peak wavelength of about 500 nm to about 560 nm (e.g., about 510 nm to about 550 nm), or vice versa (i.e., the first light may be green light and the second light may be red light).

[0236] The substrate may be a substrate including an insulating material. The substrate may include the following materials: glass; various polymers such as polyesters (e.g., poly(ethylene terephthalate) (PET), poly(ethylene naphthalate) (PEN), etc.), polycarbonate, poly((meth)acrylate C1-C10 alkyl ester), polyimide, polyamide, or a combination thereof (e.g., a copolymer or a mixture thereof); polysiloxane (e.g., polydimethylsiloxane (PDMS)); inorganic materials such as Al 2 O 3 or ZnO; or a combination thereof, but not limited thereto. The thickness of the substrate may be desirably selected in consideration of the substrate material, but is not particularly limited. The substrate may be flexible. The substrate may have a transmittance of greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 80%, or greater than or equal to about 90% for light emitted from the quantum dots.

[0237] At least a portion of the substrate may be configured to cut off (absorb or reflect) blue light. A layer capable of blocking (e.g., absorbing or reflecting) blue light, also referred to herein as a "blue cutoff layer" or "blue light absorbing layer", may be disposed on a surface of the substrate, such as at least one surface. For example, the excitation light cutoff layer (blue light absorbing layer) may include an organic material and a predetermined dye, such as a yellow dye or a dye capable of absorbing blue light and transmitting green light, red light, or green light and red light.

[0238] In an embodiment, a method of manufacturing the stacked structure comprises:

[0239] forming a film of the composition described herein on a substrate;

[0240] exposing selected areas of the film to light (e.g., having a wavelength of less than or equal to about 400 nm); and

[0241] The exposed film was developed with an alkaline developing solution to obtain a pattern of the quantum dot-polymer composite.

[0242] The details of the substrate and the composition are the same as described herein. The aforementioned composition is coated on the substrate to a predetermined thickness with appropriate methods such as spin coating, slit coating, etc. If desired, the formed film can be pre-baked (PRB). The conditions (such as temperature, duration and atmosphere) for pre-baking can be appropriately selected.

[0243] The formed (and optionally pre-baked) film is exposed to light of a predetermined wavelength (ultraviolet (UV) light) under a mask having a predetermined pattern. The wavelength and intensity of the light can be selected taking into account the type and amount of photoinitiator, the type and amount of quantum dots, etc.

[0244] The film having the selected area exposed is treated with an alkaline developing solution (e.g., sprayed or dipped), and thereby the unexposed area in the film is dissolved to provide the desired pattern, which is called development. If desired, the obtained pattern can be post-baked (POB), for example, at a temperature of about 150° C. to about 230° C. for a predetermined time, for example, greater than or equal to about 10 minutes or greater than or equal to about 20 minutes, to improve the crack resistance and solvent resistance of the pattern.

[0245] When the quantum dot polymer composite pattern has multiple (kinds of) repeating segments, a quantum dot polymer composite having a desired pattern can be obtained by preparing multiple compositions including quantum dots having desired photoluminescent properties (photoluminescent peak wavelength, etc.) (for example, quantum dots emitting red light, quantum dots emitting green light, or optionally quantum dots emitting blue light) to form each repeating segment, and repeating the pattern forming process as desired for each of the compositions (for example, twice or more, or three or more times) to form the desired pattern of the quantum dot polymer composite.

[0246] In an embodiment, a pattern may be formed using an ink composition of an embodiment including a group of cadmium-free quantum dots and a liquid carrier. For example, a pattern may be formed by depositing an ink composition including a plurality of cadmium-free quantum dots, a liquid carrier, and a monomer on a desired area of ​​a substrate, optionally removing the liquid carrier, and polymerizing.

[0247] For example, the quantum dot polymer composite may be in the form of a pattern of at least two different repeating color segments (eg, RGB segments).Such a quantum dot polymer composite pattern may be used as a photoluminescent color filter in a display device.

[0248] In an embodiment, a display device (or a light emitting element) may include a stacked structure.

[0249] When a display device including the stacked structure includes a light source, the display device may include a plurality of light emitting units corresponding to the first segment and the second segment, respectively, and the light emitting units may include a first electrode and a second electrode facing each other and an electroluminescent layer disposed between the first electrode and the second electrode.

[0250] The electroluminescent layer may include an organic light-emitting material. For example, each light-emitting unit of the light source may include an electroluminescent device (e.g., an organic light-emitting diode (OLED)) configured to emit light of a predetermined wavelength (e.g., blue light, green light, or a combination thereof). The structure and material of the electroluminescent device, such as an organic light-emitting diode (OLED), are not particularly limited.

[0251] Figure 4A is a schematic cross-sectional view of a display device according to an embodiment, and Figure 4B is a schematic cross-sectional view of a display device according to an embodiment. Figure 4A and 4B The light source includes an organic light emitting diode (OLED) that emits blue light. The organic light emitting diode OLED may include: (at least two, for example, three or more) pixel electrodes 90a, 90b, 90c formed on a substrate 100, pixel defining layers 150a, 150b formed between adjacent pixel electrodes 90a, 90b, 90c, organic light emitting layers 140a, 140b, 140c formed on the pixel electrodes 90a, 90b, 90c, and a common electrode layer 130 formed on the organic light emitting layers 140a, 140b, 140c.

[0252] A thin film transistor and a substrate may be disposed below the organic light emitting diode (OLED). Pixel regions of the OLED may be disposed corresponding to the first, second, and third segments, respectively, as described in detail herein.

[0253] A quantum dot complex pattern (e.g., comprising a first repeating segment comprising quantum dots that emit green light, a second repeating segment comprising quantum dots that emit red light, or a combination thereof) can be configured, for example, as a stacked structure that further includes a substrate, for example, configured on (e.g., directly on) a light source or configured above a light source, if the light source is present.

[0254] Light emitted from the light source (e.g., blue light, green light, or a combination thereof) may enter the second segment 21 and the first segment 11 of the pattern 170 to respectively emit (e.g., converted) red light R and green light G. Blue light B emitted from the light source passes through the third segment 31 or is transmitted from the third segment 31.

[0255] An optical element 160 may be disposed above the second segment 21 emitting red light, the first segment 11 emitting green light, or a combination thereof. The optical element may be an excitation light cutoff layer or a first filter that cuts off (e.g., reflects or absorbs) excitation light (e.g., blue light, green light, or a combination thereof). The excitation light cutoff layer or optical element 160 may be disposed on the upper substrate 240. The excitation light cutoff layer 160 may be disposed below the upper substrate 240 (e.g., on the bottom surface of the upper substrate 240). The excitation light cutoff layer 160 may be disposed between the upper substrate 240 and the quantum dot polymer composite pattern and above the first segment 11 and the second segment 21, and if desired, above the third segment 31. The details of the excitation light cutoff layer are the same as those described herein for the first filter.

[0256] The display device can be obtained by separately manufacturing the stacked structure and an LED or OLED (eg, emitting blue light) and then assembling them. Alternatively, the display device can be obtained by directly forming a quantum dot polymer composite pattern on the LED or OLED.

[0257] In an embodiment, the display device may further include a lower substrate 210, an optical element (e.g., a polarizer) 300 disposed below the lower substrate 210, and a liquid crystal layer 220 between the stacked structure and the lower substrate 210. The stacked structure may be arranged in such a way that the light emitting layer (i.e., the quantum dot polymer composite pattern) faces the liquid crystal layer. The display device may further include an optical element (e.g., a polarizer) 300 between the liquid crystal layer 220 and the light emitting layer. The light source may further include an LED and optionally a light guide plate.

[0258] refer to Figure 5 In an embodiment, the display device may include a liquid crystal panel 200, a lower optical element 300 (e.g., a polarizer) disposed on the liquid crystal panel 200, below the liquid crystal panel 200, or a combination thereof, and a backlight unit including a light source 110 emitting blue light below the lower optical element 300. The backlight unit may include the light source 110 and a light guide plate 120 (edge ​​type). Alternatively, the backlight unit may be a direct light source without a light guide plate. The liquid crystal panel 200 may include a lower substrate 210, an upper substrate 240, a liquid crystal layer 220 between the upper and lower substrates, and a light emitting layer (color filter layer) 230 disposed on or below the upper substrate 240. The light emitting layer 230 may include the quantum dot polymer composite (or a pattern thereof).

[0259] A wiring board 211 is provided on an inner surface, for example, an upper surface, of the lower substrate 210. The wiring board 211 may include a plurality of gate lines and data lines defining pixel regions, thin film transistors disposed adjacent to intersections of the gate lines and the data lines, and pixel electrodes for each pixel region, but is not limited thereto. Details of such a wiring board are not particularly limited.

[0260] The liquid crystal layer 220 may be disposed on the circuit board 211. The liquid crystal layer 220 may include an alignment layer 221 on the upper surface of the liquid crystal layer 220 and on the lower surface of the liquid crystal layer 220 to initially align the liquid crystal material included therein. There is no particular limitation on the details of the liquid crystal material, the alignment layer material, the method of forming the alignment layer, the method of forming the liquid crystal layer, the thickness of the liquid crystal layer, etc.

[0261] In an embodiment, an upper optical element or an upper polarizer 300 may be provided between the liquid crystal layer 220 and the upper substrate 240. For example, the upper optical element or the upper polarizer 300 may be provided between the liquid crystal layer 220 (or the common electrode 231) and the light emitting layer (or the quantum dot polymer composite pattern). The black matrix 241 may be provided below the upper substrate 240 (for example, on its lower surface). The openings in the black matrix 241 are aligned with the gate lines, data lines, and thin film transistors of the wiring board 211 on the lower substrate 210 (or provided to hide the gate lines, data lines, and thin film transistors of the wiring board 211 on the lower substrate 210). A second segment (R) including a color filter emitting red light, a first segment (G) including a color filter emitting green light, a third segment (B) including a color filter for emitting or transmitting blue light, or a combination thereof may be provided in the openings in the black matrix 241 (BM). For example, the black matrix 241 may have a lattice shape. If desired, the light emitting layer may further include a fourth repeating segment, such as at least one fourth repeating segment. The fourth repeating segment may be configured to emit light having a color different from the color of light emitted from the first to third segments (e.g., cyan, magenta, yellow, etc.).

[0262] The light emitting layer (color filter layer) 230 may be on the transparent common electrode 231 .

[0263] If desired, the display device may further include an excitation light cutoff layer (e.g., a blue cutoff filter or a green cutoff filter) 310, hereinafter, also referred to as a first filter layer 310. The first filter layer 310 may be disposed between the upper surfaces of the second segment (R) and the first segment (G) and the lower surface of the upper substrate 240, or on the upper surface of the upper substrate (240). The first filter layer 310 may include a sheet having an opening corresponding to the third segment (B) (e.g., a pixel region displaying, for example, emitting a blue color), and may be formed on portions corresponding to the first and second segments (G, R). The first filter layer 310 may be formed as an integral structure over portions of the light emitting layer 230 that correspond to the first and second segments (G, R) and that are different from the portion overlapping the third segment, but is not limited thereto. Alternatively, at least two first filter layers may be spaced apart from each other and may be disposed respectively over each of the portions overlapping the first and second segments.

[0264] For example, the first filter layer may block light having a predetermined wavelength range within the visible light range and may transmit light having another wavelength range. For example, the first filter layer may block blue (or green) light and transmit light other than blue light (or other than green light). For example, the first filter layer may transmit green light, red light, or yellow light (e.g., mixed light of green light and red light).

[0265] The first filter layer may include a polymer film containing a dye that absorbs light having a specific wavelength, i.e., a wavelength to be blocked, a pigment that absorbs light having a specific wavelength, i.e., a wavelength to be blocked, or a combination thereof. The first filter layer may block at least 80%, at least 90%, or at least 95% of blue light having a wavelength less than or equal to about 480 nm. For visible light having other wavelengths, the first filter layer may have a light transmittance greater than or equal to about 70%, such as greater than or equal to about 80%, greater than or equal to about 90%, or up to 100%.

[0266] The first filter layer may absorb and substantially block blue light having a wavelength less than or equal to about 500 nm, and may selectively transmit green light or red light, for example. At least two first filter layers may be spaced apart and disposed on portions overlapping the first and second segments, respectively. For example, a first filter layer that selectively transmits red light may be disposed on a portion overlapping a segment emitting red light, and a first filter layer that selectively transmits green light may be disposed on a portion overlapping a segment emitting green light. If the excitation light includes blue light and green light, a first filter that blocks green light and transmits blue light may be disposed above a segment emitting blue light.

[0267] In an embodiment, the first filter layer may include a first region, a second region, or a combination thereof. The first region of the first filter layer blocks (e.g., absorbs) blue light and red light, and transmits light having a wavelength in a predetermined range, for example, greater than or equal to about 500 nm, greater than or equal to about 510 nm, or greater than or equal to about 515 nm and less than or equal to about 550 nm, less than or equal to about 540 nm, less than or equal to about 535 nm, less than or equal to about 530 nm, less than or equal to about 525 nm, or less than or equal to about 520 nm. The second region of the first filter layer blocks (e.g., absorbs) blue light and green light, and transmits light having a wavelength in a predetermined range, for example, greater than or equal to about 600 nm, greater than or equal to about 610 nm, or greater than or equal to about 615 nm and less than or equal to about 650 nm, less than or equal to about 640 nm, less than or equal to about 635 nm, less than or equal to about 630 nm, less than or equal to about 625 nm, or less than or equal to about 620 nm. The first region of the first filter layer may be (directly) disposed at or above a position overlapping with a segment emitting green light, and the second region of the first filter layer may be (directly) disposed at or above a position overlapping with a segment emitting red light. The first region and the second region may be optically isolated from each other, for example, by a black matrix. The first filter layer may contribute to improving the color purity of the display device.

[0268] The first filter layer may be a reflective filter including a plurality of layers (e.g., inorganic material layers) each having a different refractive index. For example, in the first filter layer, two layers having different refractive indices may be alternately stacked with each other. For example, a layer having a high refractive index and a layer having a low refractive index may be alternately stacked with each other.

[0269] The display device may further include a second filter layer 311 (e.g., a red / green light or yellow light recycling layer) disposed between the light emitting layer 230 and the liquid crystal layer 220, and between the light emitting layer 230 (e.g., the quantum dot polymer composite layer) and the upper polarizer 300. The second filter layer 311 may transmit at least a portion of the third light, and reflect at least a portion of the first light, the second light, or the first light and the second light. The second filter layer may reflect light having a wavelength greater than 500 nm. The first light may be green (or red) light, the second light may be red (or green) light, and the third light may be blue light.

[0270] The quantum dots can be used in quantum dot-based electroluminescent devices (see Figure 6) in the light-emitting layer in. The electroluminescent device may include: an anode 1 and a cathode 5 facing each other; a quantum dot emission layer 3 disposed between the anode and the cathode and including a plurality of quantum dots, and a hole auxiliary layer 2 disposed between the anode and the quantum dot emission layer. The hole auxiliary layer may include a hole injection layer (HIL), a hole transport layer (HTL), an electron blocking layer (EBL), or a combination thereof. The hole auxiliary layer may include a suitable organic / inorganic material with hole properties. The electroluminescent device may further include an electron auxiliary layer 4 between the cathode and the quantum dot emission layer. The electron auxiliary layer may include an electron injection layer (EIL), an electron transport layer (ETL), a hole blocking layer (HBL), or a combination thereof. The electron auxiliary layer may include a suitable organic / inorganic material with electronic properties.

[0271] Hereinafter, the embodiments are described in more detail with reference to Examples. However, they are illustrative examples of the present disclosure, and the present disclosure is not limited thereto.

[0272] Example

[0273] Analytical methods

[0274] 1. Photoluminescence Analysis

[0275] Photoluminescence (PL) spectra of the fabricated nanocrystals were obtained using a Hitachi F-7000 spectrometer at a radiation wavelength of 372 nanometers (nm).

[0276] 2. Ultraviolet (UV) spectroscopy analysis

[0277] UV spectroscopy analysis was performed using an Agilent Cary 5000 spectrometer to obtain UV-visible absorption spectra.

[0278] 3. Inductively coupled plasma (ICP) analysis

[0279] Inductively coupled plasma-atomic emission spectrometry (ICP-AES) analysis was performed using Shimadzu ICPS-8100.

[0280] 4. Transmission Electron Microscopy (TEM) Analysis

[0281] TEM analysis was performed using a UT F30 Tecnai electron microscope.

[0282] 5. X-ray Photoelectron Spectroscopy (XPS) Analysis

[0283] X-ray photoelectron spectroscopy analysis was performed using Quantum2000 manufactured by Physical Electronics.

[0284] The synthesis was performed under an inert gas atmosphere (nitrogen flowing condition) unless otherwise mentioned.

[0285] Embodiment 1:

[0286] Selenium and tellurium were dispersed in trioctylphosphine (TOP) to obtain 0.4 molar (M) Se / TOP stock solution and 0.5M Te / TOP stock solution. The Te / TOP stock solution, an organic ligand including oleylamine, and lithium aluminum hydride were mixed at room temperature to prepare a mixed solution.

[0287] In a 300 milliliter (mL) reaction flask, 0.9 mmol of zinc acetate was dissolved in octadecene together with oleic acid and heated under vacuum at 120° C. Within one hour, the atmosphere in the reactor was changed to an inert gas, and the reaction system was heated to 300° C.

[0288] The Se / TOP stock solution and the mixed solution were injected into the heated reaction system, and the reaction was carried out and terminated.

[0289] The reactor was cooled to room temperature, and acetone was added thereto to obtain a precipitate, which was separated via centrifugation to provide ZnTeSe cores. The obtained ZnTeSe cores were dispersed in toluene.

[0290] The amounts of Zn and Se precursors used relative to 1 mol of Te were controlled to provide a desired composition (eg, as ICP results described below) in consideration of the respective reactivities of the precursors. The amount of the hydride compound used was 1 mol relative to 1 mol of Te.

[0291] Sulfur was dispersed in trioctylphosphine (TOP) to obtain a 1 molar (M) S / TOP stock solution.

[0292] In a 300 mL reaction flask, trioctylamine (TOA) was placed, and zinc acetate and oleic acid were added thereto, and then the mixture was heated at 120° C. for one hour under vacuum. Then, the atmosphere in the flask was replaced with an inert atmosphere, and the flask was heated over 250° C.

[0293] Prepare a solution of zinc chloride in acetone (concentration 1 M).

[0294] The prepared ZnTeSe cores, S / TOP stock solution, and acetone solution of zinc chloride were added to the heated reaction system, and the reaction was performed for 10 minutes.

[0295] After the reaction was completed, the flask was cooled to room temperature, and acetone was added thereto to produce a precipitate, from which the ZnTeSe / ZnS:Cl core-shell quantum dots were collected via centrifugation. The obtained core-shell quantum dots were dispersed in toluene.

[0296] 2.14 mol of sulfur was used per 1 mol of the Te precursor, and 0.4 mol of the Cl precursor was used per 1 mol of the sulfur.

[0297] For the as-prepared core and core-shell quantum dots, TEM analysis was performed and the results are shown in Table 1.

[0298] For the as-prepared core and core-shell quantum dots, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1. The valley depth (VD) of the core-shell quantum dots was about 0.21.

[0299] For the as-prepared core-shell quantum dots, ICP-AES analysis was performed and the results are shown in Table 2.

[0300] The amount of aluminum to tellurium in the quantum dots was about 0.14. XPS analysis was performed on the core-shell quantum dots prepared in this way, and the results confirmed that substantially no peak attributable to tellurium oxide was found. The results of the XPS analysis confirmed that the molar ratio of Cl to Te was about 0.15:1.

[0301] Example 1-1:

[0302] Core-shell quantum dots were prepared in the same manner as in Example 1, except that an acetone solution of zinc chloride was used during the formation of the core. Se / TOP stock solution and the mixed solution were injected into the heated reaction medium, and the acetone solution was added thereto. ICP-AES analysis was performed and chlorine was detected.

[0303] Comparative Example 1:

[0304] ZnTeSe / ZnS core-shell quantum dots were prepared in the same manner as in Example 1, except that during shell formation, an acetone solution of zinc chloride was not used.

[0305] For the as-prepared core and core-shell quantum dots, TEM analysis was performed and the results are shown in Table 1.

[0306] For the as-prepared core and core-shell quantum dots, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1. For the as-prepared core-shell quantum dots, ICP AES analysis was performed, and the results confirmed that chlorine was not detected.

[0307] XPS analysis was performed on the core-shell quantum dots thus prepared, and the results confirmed that tellurium oxide (or TeO 3 ) peak.

[0308] Embodiment 2:

[0309] ZnTeSe / ZnSe:Cl core-shell quantum dots were prepared in the same manner as in Example 1, except that Se / TOP was used instead of S / TOP during shell formation.

[0310] In addition, 0.43 mol of selenium was used per 1 mol of the Te precursor, and 0.4 mol of the Cl precursor was used per 1 mol of the selenium.

[0311] For the core and core-shell quantum dots as prepared, TEM analysis was performed and the results are shown in Tables 1 and Fig. 7A middle.

[0312] For the as-prepared core and core-shell quantum dots, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1. The valley depth (VD) of the core-shell quantum dots was about 0.13.

[0313] For the as-prepared core-shell quantum dots, ICP AES analysis was performed and the results are shown in Table 2.

[0314] The results of XPS analysis confirmed that the molar ratio of Cl to Te was about 0.4:1.

[0315] For the core-shell quantum dots as prepared, ICP-AES analysis was performed and the results are shown in Table 2. The amount of aluminum relative to tellurium of the quantum dots was about 0.21.

[0316] Comparative Example 2-1:

[0317] ZnTeSe / ZnSe core-shell quantum dots were prepared in the same manner as in Example 2, except that during shell formation, an acetone solution of zinc chloride was not used and the reaction time was increased by about 30 minutes. The core-shell quantum dots thus obtained were dispersed in toluene.

[0318] For the core and core-shell quantum dots as prepared, TEM analysis was performed and the results are shown in Tables 1 and Figure 7B middle.

[0319] For the as-prepared core and core-shell quantum dots, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1. For the as-prepared core-shell quantum dots, ICP AES analysis was performed and the results confirmed that no chlorine was detected.

[0320] Comparative Example 2-2:

[0321] ZnTeSe / ZnSe core-shell quantum dots were prepared in the same manner as in Example 2, except that during shell formation, HF solution was used instead of the acetone solution. The core-shell quantum dots thus obtained were dispersed in toluene.

[0322] For the as-prepared core and core-shell quantum dots, TEM analysis was performed and the results are shown in Figure 8 In the experiment, it was confirmed that the quantum dots prepared in this way had irregular shapes.

[0323] For the as-prepared core and core-shell quantum dots, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1. For the as-prepared core-shell quantum dots, ICP AES analysis was performed and the results confirmed that no chlorine was detected.

[0324] Embodiment 3:

[0325] ZnTeSe / ZnSe:Cl core-shell quantum dots were prepared in the same manner as described in Example 2. The obtained core-shell quantum dots were dispersed in toluene.

[0326] Sulfur was dispersed in trioctylphosphine (TOP) to obtain a 1 molar (M) S / TOP stock solution.

[0327] In a 300 mL reaction flask, trioctylamine (TOA) was placed, and 0.9 mmol of zinc acetate and oleic acid were added thereto, and then the mixture was heated at 120° C. for one hour under vacuum. Then, the atmosphere in the flask was replaced with an inert atmosphere, and the flask was heated over 250° C.

[0328] Prepare a solution of zinc chloride in acetone (concentration 1 M).

[0329] The prepared ZnTeSe / ZnSe:Cl quantum dots, S / TOP stock solution, and acetone solution of zinc chloride were added to the heated reaction system, and the reaction was performed for 30 minutes.

[0330] After the reaction was completed, the flask was cooled to room temperature, and acetone was added thereto to produce a precipitate, from which the ZnTeSe / ZnSe:Cl / ZnS:Cl core-shell quantum dots were collected via centrifugation. The obtained core-shell quantum dots were dispersed in toluene.

[0331] During the formation of the shell, 0.43 mol of selenium and 2.14 mol of sulfur were used per 1 mol of Te precursor, respectively. Also, 0.4 mol of Cl precursor was used per 1 mol of selenium.

[0332] For the as-prepared core and core-shell quantum dots, TEM analysis was performed and the results are shown in Table 1.

[0333] For the core and core-shell quantum dots as prepared, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1. The valley depth (VD) of the core-shell quantum dots was about 0.12. The results of the XPS analysis confirmed that the molar ratio of Cl to Te was greater than about 0.4:1.

[0334] For the as-prepared core-shell quantum dots, ICP-AES analysis was performed and the results are shown in Table 2.

[0335] Embodiment 4:

[0336] ZnTeSe / ZnS:Cl core-shell quantum dots were prepared in the same manner as in Example 1, except that during shell formation, GaCl 3 Replace ZnCl 2 .

[0337] 2.14 mol of sulfur was used per 1 mol of the Te precursor, and 0.4 mol of the Cl precursor was used per 1 mol of the sulfur.

[0338] For the as-prepared core and core-shell quantum dots, UV-visible absorption spectroscopy analysis and photoluminescence spectroscopy analysis were performed, and some of the results are summarized in Table 1.

[0339] The valley depth (VD) of the core-shell quantum dots was about 0.22. For the core-shell quantum dots as prepared, ICPAES analysis was performed and the results are shown in Table 2.

[0340] The amount of gallium to tellurium in the quantum dots was about 0.015. XPS analysis results confirmed that the molar ratio of Cl to Te was about 1.48:1.

[0341] Table 1

[0342]

[0343]

[0344] FWHM: Half Width (nm)

[0345] Circularity and solidity: average values, confirmed by Image J program of TEM results

[0346] Avg.Size: average size

[0347] PL: Photoluminescence

[0348] WL: wavelength

[0349] QY: Quantum efficiency (%)

[0350] The results of Table 1 demonstrate that the quantum dots of the embodiments may have improved luminescence properties, improved shape properties, or a combination thereof. Fig. 7A and Figure 7B The results confirmed that the addition of chlorine can lead to improved shape uniformity.

[0351] Table 2

[0352]

[0353] While the present disclosure has been described with respect to what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but, on the contrary, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

Claims

1. Core-shell quantum dots, including: A core comprising a first semiconductor nanocrystal, the first semiconductor nanocrystal comprising zinc, tellurium, and selenium; and A semiconductor nanocrystal shell is disposed on the core, the semiconductor nanocrystal shell comprising Zinc; and Selenium, sulfur, or a combination thereof, wherein the core-shell quantum dots do not include cadmium, lead, mercury, or a combination thereof, wherein the core-shell quantum dots further comprise chlorine, wherein in the core-shell quantum dots, the molar ratio of chlorine to tellurium is greater than or equal to 0.01:1, and The quantum efficiency of the core-shell quantum dots is greater than or equal to 10%.

2. The core-shell quantum dot of claim 1, wherein the molar ratio of tellurium to selenium in the core-shell quantum dot is greater than 0.4:

1.

3. The core-shell quantum dot of claim 1, wherein in the core-shell quantum dot, a molar ratio of tellurium to selenium is less than or equal to 4:

1.

4. The core-shell quantum dot of claim 1, wherein in the core-shell quantum dot, a molar ratio of chlorine to tellurium is greater than or equal to 0.05:

1.

5. The core-shell quantum dot of claim 1, wherein the core does not include a Group III-V compound containing indium or gallium.

6. The core-shell quantum dot of claim 1, wherein the core-shell quantum dot further comprises aluminum, gallium, lithium, fluorine, or a combination thereof.

7. The core-shell quantum dot of claim 1, wherein the first semiconductor nanocrystal comprises ZnTe x Se 1-x , where x is greater than or equal to 0.4 and less than or equal to 0.

9.

8. The core-shell quantum dot of claim 1, wherein the semiconductor nanocrystal shell comprises selenium and sulfur, and the molar ratio of sulfur to selenium is greater than 0:1 and less than or equal to 4:

1. 9 . The core-shell quantum dot according to claim 1 , wherein the maximum luminescence peak wavelength of the core-shell quantum dot is in the range of greater than 470 nanometers and less than or equal to 600 nanometers.

10. The core-shell quantum dot of claim 1, wherein the maximum photoluminescence peak of the core-shell quantum dot has a half-width less than or equal to 40 nanometers.

11. The core-shell quantum dot of claim 1, wherein the quantum efficiency of the core-shell quantum dot is greater than or equal to 20%.

12. The core-shell quantum dot of claim 1, wherein the core-shell quantum dot comprises an organic ligand, and the organic ligand comprises RCOOH, RNH2, R2NH, R3N, RSH, RH2PO, R2HPO, R3PO, RH2P, R2HP, R3P, ROH, RCOOR', RHPO(OH), RPO(OH)2, R2POOH, a polymer organic ligand, or a combination thereof, wherein R and R' are the same or different and are each independently a substituted or unsubstituted C1-C40 aliphatic hydrocarbon group, a substituted or unsubstituted C6-C40 aromatic hydrocarbon group, or a combination thereof.

13. A quantum dot group, comprising a plurality of core-shell quantum dots according to any one of claims 1 to 12, wherein the average circularity of the core-shell quantum dots is greater than or equal to 0.70; or The average solidity of the core-shell quantum dots is greater than or equal to 0.

8. 14 . The quantum dot group of claim 13 , wherein an average size of the core-shell quantum dots is greater than or equal to 7 nanometers.

15. A method for manufacturing a core-shell quantum dot according to any one of claims 1 to 12, comprising: preparing a zinc precursor organic solution comprising a zinc precursor and a first organic ligand in a first organic solvent; and While the zinc precursor organic solution is heated, a first selenium precursor, a tellurium precursor, a metal hydride compound, and a second organic ligand are added to the zinc precursor organic solution to prepare core particles, reacting the zinc precursor with a second selenium precursor, a sulfur precursor, or a combination thereof in a third organic solvent in the presence of a core particle and a shell-forming organic ligand to form a semiconductor nanocrystal shell on the core particle, and The chlorine precursor is added to the reaction system during the preparation of the core particle, during the formation of the semiconductor nanocrystal shell, or during the preparation of the core particle and the formation of the semiconductor nanocrystal shell. 16 . The method of claim 15 , further comprising adding a fluorine precursor to the reaction system during the preparation of the core particle, during the formation of the semiconductor nanocrystal shell, or during the preparation of the core particle and the formation of the semiconductor nanocrystal shell.

17. The method of claim 15, wherein the tellurium precursor comprises tellurium dispersed in a second organic solvent, and wherein the concentration of tellurium in the tellurium precursor is greater than 0.1 mol / L.

18. The method of claim 15, further comprising mixing the tellurium precursor, the metal hydride compound, and the second organic ligand at a temperature less than 80°C to form a mixed solution before adding to the zinc precursor organic solution.

19. The method of claim 15, further comprising preparing the chlorine precursor by dissolving a chlorine compound in a fourth organic solvent, wherein the fourth organic solvent comprises a C1-C30 alcohol, a C2-C30 ketone solvent, a C1-C40 alkylphosphine solvent, or a combination thereof.

20. Display devices, including Light emitting element, The light-emitting element comprises a plurality of core-shell quantum dots as described in any one of claims 1 to 12.

21. The display device of claim 20, wherein the light emitting element comprises a stacked structure comprising a substrate and a patterned light emitting layer, wherein the patterned light emitting layer comprises a first repeating segment configured to emit light of a predetermined wavelength, and The first repeating segment includes a plurality of the core-shell quantum dots.

22. A quantum dot composite comprising the core-shell quantum dots according to any one of claims 1 to 12.

23. A quantum dot composition comprising: The core-shell quantum dots according to any one of claims 1 to 12; and a polymerizable monomer having a carbon-carbon double bond.

24. The quantum dot composition of claim 23, wherein the polymerizable monomer is a photopolymerizable monomer.

Citation Information

Patent Citations

  • Method of 5th generation mobile telecommunication using millimeter wave band

    KR1020190129447A

  • Photosensitive compositions, quantum dot polymer composite pattern prepared therefrom, and electronic devices including the same

    US20170059988A1

  • Semiconductor nano crystal particle, manufacturing method thereof and device including the same

    CN108865109A

  • Quantum dots, and electroluminescent device and electronic device including same

    CN110240896A